Hafnium acid compound-containing material and method for producing same

The hafnic acid compound, composed of hafnium, an organic nitrogen compound, and a solvent, addresses the dispersibility issues of crystalline hafnia sol by enhancing solubility and stability, enabling effective compounding and film formation with improved transmittance.

JP7603196B1Active Publication Date: 2024-12-19MITSUI MINING & SMELTING CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024527500
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-02-03
Filing Date
2024-02-02
Publication Date
2024-12-19
Estimated Expiration
2044-02-02

AI Technical Summary

Technical Problem

The crystalline hafnia sol disclosed in existing technologies is acidic and difficult to complex with basic metal elements, making it unsuitable for compounding and film formation.

Method used

A hafnic acid compound-containing material is developed, comprising hafnium, an organic nitrogen compound, and a solvent, which is heated in a vacuum atmosphere to enhance dispersibility, with a specific XRD intensity ratio and transmittance characteristics.

Benefits of technology

The hafnic acid compound exhibits improved dispersibility and solubility in solvents, allowing for effective compounding and film formation, and has a unique crystal structure with enhanced stability and transmittance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603196000001
    Figure 0007603196000001
  • Figure 0007603196000002
    Figure 0007603196000002
  • Figure 0007603196000003
    Figure 0007603196000003
Patent Text Reader

Abstract

The hafnium oxide compound-containing material of the present invention contains hafnium, an organic nitrogen compound, and a solvent, and the ratio Ib / Ia of the XRD maximum intensity (Ib) at a diffraction angle 2θ of 5° to 6° to the XRD maximum intensity (Ia) at a diffraction angle 2θ of 31° to 33° of a dried powder obtained by drying the hafnium oxide compound-containing material in a vacuum atmosphere for 15 hours at 150°C is 1.2 or more. Also, the hafnium oxide compound-containing material of the present invention contains hafnium, an organic nitrogen compound, and a solvent, and has a maximum transmittance of 70%T or more in a wavelength range of 550nm to 700nm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hafnium acid compound-containing material and a method for producing the same. [Background technology]

[0002] Hafnium oxide, for example, hafnium (IV) oxide and its composites, have been used as gate insulating films in transistors and the like because of their high relative dielectric constant characteristics. In addition, hafnium (IV) oxide is expected to realize extremely thin and low-voltage ferroelectric memories as a ferroelectric material. Furthermore, hafnium (IV) oxide is used as an insulating heat-resistant material for thermocouples and the like, making use of the extremely high melting point of hafnium (IV) oxide. For example, Patent Document 1 discloses a crystalline hafnia sol containing powdered hafnium (IV) oxide, i.e., hafnia powder. The crystalline hafnia sol is finely divided and monodispersed, and can be used as a raw material for refractories, insulators, derivatives, and the like. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2007-223881 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the crystalline hafnia sol disclosed in Patent Document 1 is an acidic sol containing nitric acid, and therefore it is difficult to form a composite with a liquid containing other basic metal elements, and the inclusion of oxoacids or halogen ions makes it unsuitable for forming a composite or a film.

[0005] In view of the above problems, the present invention provides a basic, highly dispersible hafnium acid compound-containing material and a method for producing the same. [Means for solving the problem]

[0006] The hafnium acid compound-containing material of the present invention, which has been made to solve the above problems, is a hafnium acid compound-containing material containing hafnium, an organic nitrogen compound, and a solvent, and is characterized in that the hafnium acid compound-containing material is dried at 150°C for 15 hours under a vacuum atmosphere, and the dried powder is obtained by drying the hafnium acid compound-containing material at 150°C for 15 hours under a vacuum atmosphere, and the ratio Ib / Ia of the XRD maximum intensity (Ib) at a diffraction angle 2θ = 5° to 6° to the XRD maximum intensity (Ia) at a diffraction angle 2θ = 31° to 33° is 1.1 or more. The hafnium acid compound-containing material of the present invention is a hafnium acid compound-containing material containing hafnium, an organic nitrogen compound, and a solvent, and from the viewpoint of excellent dispersibility, it is preferable that the ratio Ib / Ia of the XRD maximum intensity (Ib) at a diffraction angle 2θ=5° to 6° to the XRD maximum intensity (Ia) at a diffraction angle 2θ=31° to 33° of the dried powder obtained by drying the hafnium acid compound-containing material at 150° for 15 hours under a vacuum atmosphere is 1.1 or more.

[0007] It is presumed that hafnium in the hafnium acid compound-containing material of the present invention exists in the material as ions formed by multi-stage condensation of hafnium atoms and oxygen atoms in the material.

[0008] The hafnium acid compound-containing material of the present invention contains an organic nitrogen compound in addition to hafnium. The "organic nitrogen compound" of the present invention also includes the one ionized in the hafnium acid compound-containing material of the present invention. As will be described in detail later in the manufacturing method of the hafnium acid compound-containing material of the present invention, in the manufacturing process, an acidic hafnium solution is added to ammonia water by reverse neutralization method to generate a hydrated ammonium hafnate cake, which is a hafnium-containing precipitate slurry, and then an organic nitrogen compound is added and mixed to generate the hafnium acid compound-containing material of the present invention, so that it is considered that the substituted organic nitrogen compound exists in the inclusion as a cation.

[0009] Examples of the solvent for the hafnium acid compound-containing material of the present invention include water and organic solvents. Examples of the organic solvent include alcohol solvents, ketone solvents, ether solvents, ester solvents, aromatic hydrocarbon solvents, aliphatic hydrocarbon solvents, etc., and these organic solvents may be mixed with water. Examples of the alcohol solvent include alcohols having 5 or less carbon atoms (methanol, ethanol, n-propanol, isopropyl alcohol, butanol, ethylene glycol, propylene glycol, glycerin), acetone, etc.

[0010] The hafnium acid compound-containing material of the present invention is preferably such that the ratio Ib / Ia of the XRD maximum intensity (Ib) at a diffraction angle 2θ=5° to 6° inclusive to the XRD maximum intensity (Ia) at a diffraction angle 2θ=31° to 33° inclusive of the dried powder obtained by drying the hafnium acid compound-containing material at 150° for 15 hours under a vacuum atmosphere is 1.1 or more, more preferably 1.2 or more, from the viewpoint of excellent solubility of the hafnium acid compound in solvents.

[0011] Here, commonly available hafnium oxide has a monoclinic crystal structure at room temperature and normal pressure, and its XRD spectrum is characterized by having two peaks with maximum intensity near the diffraction angle 2θ=28°-32°, referring to Card No.: 00-034-0104 Quality: S. On the other hand, the XRD spectrum of the dried powder obtained by drying the hafnium acid compound-containing material of the present invention as described above has a unique pattern with maximum intensity near the diffraction angle 2θ=5°-6°, as shown in FIG. 3, which is stronger than the maximum intensity near the diffraction angle 2θ=31°-33°, so it is presumed to have a crystal structure different from that of commonly available hafnium oxide, for example, a plurality of crystal structures including an amorphous structure. Furthermore, it is presumed that when the hafnium oxide compound-containing material of the present invention has a ratio Ib / Ia (the ratio of the XRD maximum intensity (Ib) to the XRD maximum intensity (Ia) of the dry powder of 1.1 or more, more preferably 1.2 or more, the solubility in solvents is improved compared to commonly available hafnium oxide.

[0012] The XRD maximum intensity (Ia) and the XRD maximum intensity (Ib) of the hafnic acid compound-containing material of the present invention can be measured by dividing 100g of the hafnic acid compound-containing material of the present invention into a 100mL Teflon (registered trademark) beaker, drying it under vacuum at 150°C for 15 hours, and carrying out the measurement of the obtained dry powder under the following powder X-ray diffraction measurement conditions. Then, the ratio Ib / Ia of the XRD maximum intensity (Ib) to the XRD maximum intensity (Ia) of the dry powder is calculated.

[0013] = Powder X-ray diffraction measurement conditions = Diffraction equipment: MiniFlex2 (Rigaku Corporation) ·X-ray tube: Cu Tube voltage / current: 30kV, 15mA ·Slit: DS-SS; 1.25 degree, RS; 0.3mm Monochromator graphite Measurement interval: 0.01 degree Counting method: Constant counting method X-ray analysis software: PDXL2 Version 2.9.1.0

[0014] In addition, when the hafnium oxide compound-containing material of the present invention is dried under vacuum to obtain a dry powder, the crystal phase of the dry powder obtained changes depending on the heating temperature. For example, when the heating temperature is 150°C, the crystal structure of the dry powder is a plurality of crystal structures including an amorphous structure, whereas when the heating temperature is, for example, 800°C, sintering in an air atmosphere and then cooling to room temperature (25°C), the crystal structure of the dry powder converges to a monoclinic crystal.

[0015] The change in the crystal phase in the hafnium oxide compound-containing material of the present invention can also be observed by the half-width of the XRD maximum intensity (Ia). Since hafnium oxide having a monoclinic crystal structure has a single crystal structure, the half-width of the XRD maximum intensity (Ia) tends to be narrow. On the other hand, the crystal structure of the dried powder changes, and the half-width tends to be broad.

[0016] In the present invention, the term "content" refers to a liquid or a liquid containing a gel as described below. Furthermore, the liquid is not limited to a solute dispersed or mixed in a solvent in a monomolecular state, but also includes an aggregate in which a plurality of molecules are attracted to each other by intermolecular interactions, such as (1) polymer molecules, (2) solvated molecules, (3) molecular clusters, and (4) colloidal particles dispersed in a solvent.

[0017] The hafnium oxide compound-containing material of the present invention contains hafnium, an organic nitrogen compound, and a solvent, and has a maximum transmittance of 70%T or more in a wavelength range of 550 nm to 700 nm. of It is characterized by: The hafnium acid compound-containing material of the present invention is a hafnium acid compound-containing material containing hafnium, an organic nitrogen compound, and a solvent, and it is preferable from the viewpoint of excellent dispersibility that the maximum transmittance in the wavelength range of 550 nm to 700 nm is 70%T or more.

[0018] As described above, the hafnium acid compound-containing material of the present invention contains hafnium, an organic nitrogen compound, and a solvent.

[0019] Furthermore, the hafnium acid compound-containing material of the present invention is preferably such that the maximum transmittance in the wavelength region of 550 nm to 700 nm is 70%T or more, from the viewpoint of excellent solubility of the hafnium acid compound in the solvent. Also, the maximum transmittance in the wavelength region of 550 nm to 700 nm is more preferably 75%T or more, more preferably 80%T or more, particularly preferably 85%T or more, more preferably 90%T or more, more preferably 95%T or more, particularly preferably 98%T or more, more preferably 99%T or more, and most preferably 100%T or more. Note that if the measured value exceeds 100%T due to measurement error of the spectrophotometer used to measure the transmittance, it is considered to be 100%T.

[0020] In addition, the hafnium acid compound-containing material of the present invention preferably has at least one of the transmittances at wavelengths of 550 nm, 600 nm, 650 nm, and 700 nm of 70% T or more, more preferably 75% T or more, even more preferably 80% T or more, and particularly preferably 85% T or more. Ku , more preferably 90%T or more, even more preferably 95%T or more, particularly preferably 98%T or more, even more preferably 99%T or more, and most preferably 100%T or more. Note that if the measured value exceeds 100%T due to measurement error of the spectrophotometer used to measure the transmittance, it is considered to be 100%T.

[0021] Furthermore, the hafnium acid compound-containing material of the present invention preferably has a minimum transmittance in the wavelength region of 550 nm to 700 nm of 70% T or more, more preferably 75% T or more, even more preferably 80% T or more, particularly preferably 85% T or more, more preferably 90% T or more, even more preferably 95% T or more, particularly preferably 98% T or more, even more preferably 99% T or more, and most preferably 100% T or more. Note that if the measured value exceeds 100% T due to measurement error of the spectrophotometer used to measure the transmittance, it is considered to be 100% T.

[0022] Thus, the liquid in which the maximum transmittance of the hafnic acid compound-containing material of the present invention in the wavelength region of 400 nm to 700 nm is 70%T or more is defined as the "hafnic acid compound-containing material" of the present invention. Furthermore, in this specification, unless otherwise specified, "transmittance" includes both "initial transmittance" indicating the transmittance of the hafnic acid compound-containing material of the present invention adjusted to a liquid temperature of 25°C immediately after production, and "temporary transmittance" indicating the transmittance of the hafnic acid compound-containing material of the present invention after being left to stand for one month from the day of production in an incubator set at room temperature of 25°C.

[0023] The transmittance of the hafnium acid compound-containing material of the present invention in the wavelength region of 550 nm to 700 nm is measured by placing the material adjusted to room temperature (25°C) in a quartz cell with an optical path length of 5.0 mm and using a spectrophotometer under the following transmittance measurement conditions in accordance with JIS K 0115, 2004 "General rules for absorptiometric analysis method".

[0024] =Transmittance measurement conditions= Measurement equipment: UV-Vis-NIR spectrophotometer UH4150 (manufactured by Hitachi High-Tech Science Corporation) Measurement mode: Wavelength scan Data mode: %T (transparent) Measurement wavelength range: 200~2,600nm Scan speed: 600nm / min Sampling interval: 2nm

[0025] In addition, the hafnium content in the hafnium oxide compound-containing material of the present invention is HfO 2 It is characterized in that the content is more than 0 to 10 mass % in terms of mass conversion. The hafnium content in the hafnium acid compound-containing material of the present invention is HfO 2 The hafnium content in the hafnium oxide compound-containing material is preferably more than 0 to 10 mass % in terms of improving the stability of the content. 2 In terms of conversion, it is more preferable that the content is 0.1 to 10 mass %.

[0026] Here, the hafnium content in the hafnium oxide compound-containing material of the present invention is determined by diluting the material appropriately with dilute hydrochloric acid as necessary, and measuring the hafnium oxide content in accordance with JIS K0116:2014 using high-frequency inductively coupled plasma optical emission spectrometry (ICP optical emission spectrometry (AG-5110 manufactured by Agilent Technologies)). 2 The hafnium in the hafnium oxide compound-containing material of the present invention is not necessarily HfO 2 The hafnium content is not present in the HfO 2The conversion is based on the convention for indicating hafnic acid content.

[0027] Furthermore, the hafnium acid compound-containing material of the present invention may contain hydrogen peroxide in addition to the above-mentioned hafnium, organic nitrogen compound, and solvent. The "hydrogen peroxide" according to the present invention includes hydrogen peroxide ionized in the hafnium acid compound-containing material of the present invention. As will be described in detail later in the manufacturing method of the hafnium acid compound-containing material of the present invention, it is believed that the addition of hydrogen peroxide to an acidic hafnium solution in the manufacturing process causes the anion species containing hafnium to be complexed, forming a peroxo complex with excellent dissolution stability.

[0028] The amount of hydrogen peroxide present in the substance is quantitatively analyzed, for example, by measuring the absorbance of the substance at a wavelength of 410 nm using a spectrophotometer (U-2900, manufactured by Hitachi, Ltd.) to quantify the amount of hydrogen peroxide present in the substance.

[0029] The hafnium acid compound-containing material of the present invention may contain water in addition to the above-mentioned hafnium and organic nitrogen compound. The hafnium acid compound in the hafnium acid compound-containing material of the present invention has high dispersibility in water and good solubility in water, so that pure water can be used as the solvent.

[0030] The hafnium acid compound-containing material of the present invention is characterized in that the organic nitrogen compound is a quaternary ammonium compound. The organic nitrogen compound is preferably a quaternary ammonium, which not only has high solubility but also has high crystallization suppression and high sol formation suppression.

[0031] Examples of quaternary ammonium include alkylimidazolium, pyridinium, pyrrolidium, tetraalkylammonium, etc. Specific examples of alkylimidazolium include 1-methyl-3-methylimidazolium, 1-ethyl-3-methylimidazolium, 1-propyl-3-methylimidazolium, 1-butyl-3-methylimidazolium, 1-hexyl-3-methylimidazolium, 1-methyl-2,3-dimethylimidazolium, 1-ethyl-2,3-dimethylimidazolium, 1-propyl-2,3-dimethylimidazolium, 1-butyl-2,3-dimethylimidazolium, etc. Specific examples of pyridinium and pyrrolidium include N-butyl-pyridinium, N-ethyl-3-methyl-pyridinium, N-butyl-3-methyl-pyridinium, N-hexyl-4-(dimethylamino)-pyridinium, N-methyl-1-methylpyrrolidinium, and N-butyl-1-methylpyrrolidinium. Specific examples of tetraalkylammonium include tetramethylammonium, tetraethylammonium, tetrabutylammonium, ethyl-dimethyl-propylammonium, and choline. Examples of anions that form salts with the above-mentioned cations include OH, - , Cl - , Br - , I - , B.F. 4 - , HSO 4 - etc.

[0032] The organic nitrogen compounds in the materials can be measured by gas chromatography (GC), liquid chromatography (LC), mass spectrometry (MS), gas chromatography-mass spectrometry (GC-MS), liquid chromatography-mass spectrometry (LC-MS), etc. 2 A method of quantitatively determining the amount of the heat-transfer component using a thermal conductivity meter may also be used in combination.

[0033] In addition, in the hafnium acid compound-containing material of the present invention, the quaternary ammonium is tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), choline, benzyltrimethylammonium hydroxyl, D The present invention is characterized in that the composition is one or more selected from the following: The quaternary ammonium is TMAH, TEAH, choline, benzyltrimethylammonium hydroxyl D It is preferable that the material is one or more selected from the following:

[0034] The quaternary ammonium salts include TMAH, TEAH, choline, and benzyltrimethylammonium hydroxyl. D The above may be used in combination of two or more of the above, rather than one selected from the above. Specifically, TMAH and TEAH, TMAH and choline, TMAH and benzyltrimethylammonium hydroxylase D Mixtures of two quaternary ammonium salts, such as TMAH, TEAH, and choline, and mixtures of three quaternary ammonium salts, such as TMAH, TEAH, choline, and benzyltrimethylammonium hydroxylase. D Examples include mixtures of four types of quaternary ammonium.

[0035] In addition, the hafnic acid compound-containing material of the present invention preferably has a pH of more than 7. The hafnic acid compound-containing material of the present invention has a pH of more than 7 because the material has better stability. The pH is more preferably 10 or more, even more preferably 11 or more, particularly preferably 12 or more, even more particularly preferably 13 or more, and may be 14 or more. In this specification, unless otherwise specified, "pH" refers to both "initial pH", which is the pH of the hafnic acid compound-containing material of the present invention adjusted to a liquid temperature of 25°C immediately after production, and "pH over time", which is the pH of the hafnic acid compound-containing material of the present invention after being left to stand for one month from the day of production in an incubator set at room temperature of 25°C.

[0036] Here, the pH of the hafnium acid compound-containing material of the present invention is measured by immersing an electrode (HORIBA: Standard ToupH electrode 9615S-10D) of a pH meter (HORIBA: Glass electrode type hydrogen ion concentration indicator D-51) in the hafnium acid compound-containing material of the present invention, and then confirming that the liquid temperature has stabilized at 25°C.

[0037] The hafnium acid compound-containing material of the present invention may further contain a resin. The hafnium acid compound-containing material of the present invention is preferably one that contains a resin, since the resin is uniformly compatible with the hafnium acid compound and acts to adhere to the substrate, thereby improving the film-forming properties and adhesion to the substrate.

[0038] Examples of the resin contained in the material containing a hafnium acid compound include polyolefin-based compounds and polyvinyl-based compounds.

[0039] Furthermore, the resin contained in the hafnium acid compound-containing material of the present invention may be an anionic water-soluble resin and / or a nonionic water-soluble resin. When the resin contained in the hafnium acid compound-containing material of the present invention is an anionic water-soluble resin and / or a nonionic water-soluble resin, the anionic water-soluble resin and / or the nonionic water-soluble resin is uniformly compatible with the above-mentioned hafnium acid compound and acts to adhere to the substrate, thereby improving the film-forming property and adhesion to the plastic film substrate.

[0040] Here, the cationic water-soluble resin is a resin that has a positive charge in the polymer in water of pH=7, and has a functional group of, for example, any one of amino group, imino group, tertiary amine group, quaternary ammonium group, and hydrazino group. The anionic water-soluble resin is a resin that has a negative charge in the polymer in water of pH=7, and has a functional group of, for example, any one of carboxyl group, sulfone group, sulfate ester group, and phosphate ester group. Furthermore, the nonionic water-soluble resin is a resin that does not fall under the above-mentioned cationic water-soluble resin or anionic water-soluble resin, and has a functional group of, for example, any one of hydroxyl group, ether group, and amide group in the polymer.

[0041] Furthermore, these resins may contain one or more water-soluble homopolymers selected from the group consisting of acrylic polymers, urethane polymers, styrene polymers, olefin polymers, amide polymers, siloxane polymers, epoxy polymers, vinyl chloride polymers, and vinyl acetate polymers, and / or water-soluble copolymers consisting of two or more of these polymers. In particular, it is preferable that the resins contain one or more water-soluble homopolymers of acrylic polymers, styrene polymers, and olefin polymers, and / or water-soluble copolymers consisting of two or more of these polymers.

[0042] The hafnium acid compound-containing material of the present invention may further contain a high-boiling point solvent. Here, the high-boiling point solvent is preferably a solvent having a boiling point of 180° C. or higher at 1 atmospheric pressure, and examples of the high-boiling point solvent include polyhydric alcohol solvents and glycol solvents.

[0043] Here, examples of polyhydric alcohol solvents include glycerin (boiling point: 290°C), 1,6-hexanediol (boiling point: 250°C), and 1,7-heptanediol (boiling point: 259°C). Examples of glycol solvents include ethylene glycol (boiling point: 197.3°C), propylene glycol (boiling point: 188.2°C), diethylene glycol (boiling point: 244.3°C), triethylene glycol (boiling point: 287.4°C), oligoethylene glycol (boiling point: 287°C to 460°C), polyethylene glycol (PEG) (boiling point: 460°C or higher), polyethylene glycol (PEG)-polypropylene glycol (PPG) copolymer (boiling point: 460°C). or higher), diethylene glycol monohexyl ether (boiling point: 260°C), polyoxyalkylene monoalkyl ether (boiling point: 260°C or higher), polyoxyethylene sorbitan monolaurate (boiling point: 321°C or higher), other anionic fluorosurfactants (boiling point: 180°C or higher), amphoteric fluorosurfactants (boiling point: 180°C or higher), nonionic fluorosurfactants (boiling point: 180°C or higher), amine oxides (boiling point: 180°C or higher), etc. are particularly preferred. Glycerin is particularly preferred. The above boiling points are those at 1 atmospheric pressure.

[0044] In addition, since a high boiling point solvent has a high boiling point, if the boiling point at 1 atmospheric pressure is excessively high, the high boiling point solvent may decompose before boiling, making it impossible to measure the boiling point accurately. In such a case, the boiling point at reduced pressure may be measured and converted to the boiling point at 1 atmospheric pressure using a general-purpose boiling point conversion table.

[0045] Furthermore, the hafnium acid compound-containing material of the present invention may contain components other than components derived from hafnium or hafnium acid, organic nitrogen compounds, and hydrogen peroxide (hereinafter referred to as "other components") as unavoidable impurities, to the extent that the action and effect of the material is not impaired.

[0046] The hafnium acid compound-containing material of the present invention may contain additives such as dispersants, pH adjusters, colorants, thickeners, wetting agents, and binder resins, depending on the intended use.

[0047] The method for producing the above-mentioned hafnium acid compound-containing material of the present invention will be described below.

[0048] The method for producing a hafnium acid compound-containing material of the present invention is characterized by comprising the steps of: adding an acidic hafnium aqueous solution containing hafnium to an alkaline aqueous solution to produce a hafnium-containing precipitate; and adding an organic nitrogen compound to the hafnium-containing precipitate slurry obtained by turning the hafnium-containing precipitate into a slurry to produce a hafnium acid compound-containing material.

[0049] First, hydrofluoric acid (HF), such as an aqueous solution of hydrofluoric acid, is added to hafnium, hafnium oxide, or hafnium hydroxide, and the mixture is kept at 60°C to 100°C in a water bath for 1 to 72 hours to react with hafnium fluoride (HfF 4 ) and dissolving it in water to produce a hydrofluoric acid solution of a hafnium compound.

[0050] Here, the hydrofluoric acid solution of the hafnium compound is dissolved in water (e.g., pure water) to convert the hafnium to HfO 2 It is preferable to adjust the hafnium content to 1 to 100 g / L in terms of HfO 2 A hafnium content of 1 g / L or more in terms of the hafnium oxide compound hydrate is preferably soluble in water, and from the viewpoint of productivity, a hafnium content of 10 g / L or more is more preferable, and a hafnium content of 20 g / L or more is even more preferable. 2 A conversion of 100 g / L or less is preferable because it results in a hafnium oxide compound hydrate that is easily soluble in water, and in order to more reliably synthesize a hafnium oxide compound hydrate that is easily soluble in water, a conversion of 100 g / L or less is more preferable, a conversion of 90 g / L or less is even more preferable, a conversion of 80 g / L or less is even more preferable, and a conversion of 70 g / L or less is particularly preferable. Note that the pH of the hydrofluoric acid solution of the hafnium compound is preferably 2 or less, more preferably 1 or less, from the viewpoint of completely dissolving hafnium or hafnium oxide.

[0051] Next, hydrogen peroxide is added to the hydrofluoric acid solution of the hafnium compound and mixed to obtain an acidic or neutral aqueous hafnium complex solution. It is presumed that at least a portion of the hafnium contained in the obtained aqueous hafnium complex solution forms a peroxo complex.

[0052] Here, the hydrogen peroxide content of the hydrogen peroxide solution added to the hydrofluoric acid solution of the hafnium compound is preferably 0.5% by mass to 35% by mass. 2 O 2 It is preferable to add hydrogen peroxide so that / Hf is 0.6 or more and 1.5 or less, and since there is a possibility that hydrogen peroxide may decompose during mixing, it is more preferable that the ratio is 0.7 or more and 1.2 or less.

[0053] In the step of adding the hafnium complex aqueous solution to the alkaline aqueous solution to generate the hafnium-containing precipitate, the hafnium complex aqueous solution is added to the alkaline aqueous solution, for example, ammonia water, that is, a reverse neutralization method is used to obtain a precipitate slurry containing hafnium.Then, fluoride ions are removed from the obtained precipitate slurry containing hafnium, thereby obtaining a hafnium-containing precipitate from which fluoride ions have been removed.

[0054] The ammonia content of the ammonia water used for reverse neutralization is preferably 10% by mass to 30% by mass. When the ammonia content is 10% by mass, hafnium is less likely to remain undissolved, and hafnium or hafnic acid can be completely dissolved in water. On the other hand, when the ammonia content is 30% by mass or less, it is preferable because it is close to a saturated aqueous solution of ammonia.

[0055] From this viewpoint, the ammonia content of the ammonia water is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass or more, while the ammonia content is preferably 30% by mass or less, more preferably 29% by mass or less, and even more preferably 28% by mass or less.

[0056] In the reverse neutralization process, the amount of hafnium complex solution added to the ammonia water is NH 3 The molar ratio of NH / Hf is preferably 95 to 500, more preferably 100 to 450, and even more preferably 110 to 400. The amount of the hafnium complex aqueous solution added to the ammonia water is adjusted to NH 3 The molar ratio of NH / HF is preferably 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more. 3 The molar ratio of / HF is preferably 100 or less, more preferably 50 or less, and even more preferably 40 or less.

[0057] In the reverse neutralization step, the time for adding the hafnium complex aqueous solution to the ammonia water is preferably within 10 minutes, more preferably within 8 minutes, and even more preferably within 5 minutes. That is, it is preferable to add the hafnium complex aqueous solution to the ammonia water in as short a time as possible, for example, all at once, rather than gradually adding the hafnium complex aqueous solution over a long period of time, and to carry out the neutralization reaction. In addition, since the hafnium complex aqueous solution is added to the alkaline ammonia water in the reverse neutralization step, the neutralization reaction can be carried out while maintaining a high pH. The hafnium complex aqueous solution and the ammonia water can be used at room temperature.

[0058] In the reverse neutralization step, fluoride ions are removed from the hafnium-containing precipitate slurry obtained by the reverse neutralization method, thereby obtaining a hafnium-containing precipitate from which fluoride ions have been removed. The hafnium-containing precipitate slurry obtained by the reverse neutralization method contains fluorine compounds such as ammonium fluoride as impurities, and it is therefore preferable to remove these.

[0059] Any method can be used to remove the fluorine compounds, and for example, a method using a membrane such as reverse osmosis filtration, ultrafiltration, or microfiltration using ammonia water or pure water, centrifugation, or other known methods can be used. Note that when removing fluoride ions from the hafnium-containing precipitation slurry, there is no particular need to adjust the temperature, and the removal can be carried out at room temperature.

[0060] Specifically, the hafnium-containing precipitate slurry obtained by the reverse neutralization method is decanted using a centrifuge, and washed several times until the amount of liberated fluoride ions is 100 mg / L or less, thereby obtaining a hafnium-containing precipitate from which the fluoride ions have been removed. By repeating the decantation and washing several times, for example three times, the added fluoride ions are removed, and hydrogen peroxide is also removed.

[0061] The cleaning solution used to remove fluoride ions is preferably ammonia water. Specifically, ammonia water having a concentration of 1% by mass or more and 35% by mass or less is preferable. With such ammonia water, ammonia is suitable for fluoride ions, and unnecessary cost increases can be avoided.

[0062] The hafnium-containing precipitate from which the fluoride ions have been removed is diluted with pure water or the like to obtain a hafnium-containing precipitate slurry from which the fluoride ions have been removed. The hafnium content of the hafnium-containing precipitate slurry is measured by taking a portion of the hafnium-containing precipitate slurry, drying it at 110°C for 24 hours, and then calcining it at 1,000°C for 4 hours to obtain HfO 2 The HfO 2 The hafnium content of the hafnium-containing precipitate slurry can be calculated from the weight.

[0063] The hafnium-containing precipitate slurry from which the fluoride ions have been removed, an organic nitrogen compound, and pure water are mixed together and stirred at 5°C to 90°C for 0.1 to 48 hours to obtain the hafnium acid compound-containing material of the present invention.

[0064] More preferably, the organic nitrogen compound mixed with the hafnium-containing precipitation slurry is a quaternary ammonium compound, as described above.

[0065] From the viewpoint of solubility, the quaternary ammonium is preferably mixed so that the content of the quaternary ammonium in the hafnium-containing precipitation slurry is 40% by mass or less, more preferably 20% by mass or less. From the same viewpoint, the content of the quaternary ammonium compound in the hafnium-containing precipitation slurry is preferably 0.1% by mass or more, more preferably 1% by mass or more, and may be 5% by mass or more, or may be 10% by mass or more. Incidentally, TMAH, TEAH, choline, benzyltrimethylammonium hydroxyl, D It is more preferable that the material is one or more selected from the following:

[0066] In addition, the quaternary ammonium salts mixed with the hafnium-containing precipitate slurry are TMAH, TEAH, choline, benzyltrimethylammonium hydroxylase, D For example, TMAH and TEAH, TMAH and choline, TMAH and benzyltrimethylammonium hydroxylase may be used. D Mixtures of two quaternary ammonium salts, such as TMAH, TEAH, and choline, and mixtures of three quaternary ammonium salts, such as TMAH, TEAH, choline, and benzyltrimethylammonium hydroxylase. D Examples include mixtures of four types of quaternary ammonium.

[0067] The hafnic acid compound powder of the present invention is characterized by containing the hafnic acid particles contained in the hafnic acid compound-containing material of the present invention. The hafnic acid compound powder of the present invention includes a dried powder obtained by drying the hafnic acid compound-containing material of the present invention, for example, by vacuum drying, and a fired powder obtained by further firing the obtained dried powder.The hafnic acid compound powder of the present invention also includes hafnic acid compound powders having different physical properties such as crystal structure, which are generated by vacuum drying or firing the hafnic acid compound-containing material of the present invention, and may be an amorphous structure, a single crystal structure, or a polycrystalline structure.

[0068] Next, the method for producing a hafnium oxide compound powder of the present invention is characterized by having a step of drying and / or calcining the hafnium oxide compound-containing material of the present invention to produce hafnium oxide powder.

[0069] Specifically, the method for producing a dry powder of a hafnic acid compound includes placing the hafnic acid compound-containing material obtained by the above-mentioned method for producing a hafnic acid compound-containing material of the present invention in a static furnace and drying, for example vacuum drying, for 1 to 72 hours at a heating temperature of about 60°C to 200°C, thereby evaporating the water content of the hafnic acid compound-containing material of the present invention, and obtaining a dry powder of the hafnic acid compound containing hafnic acid particles contained in the hafnic acid compound-containing material of the present invention.

[0070] On the other hand, the method for producing the calcined powder of the hafnium acid compound includes vacuum drying the hafnium acid compound-containing material of the present invention as described above, placing the obtained dried powder of the hafnium acid compound in a static furnace, and calcining it in the atmosphere at a calcination temperature of 300°C or more and 1,200°C or less for a calcination time of 1 hour or more and 72 hours or less, thereby obtaining the calcined powder of the hafnium acid compound.

[0071] The hafnic acid compound powder may be obtained by pulverizing the dry powder and the calcined powder of the hafnic acid compound described above. The hafnic acid compound powder may be obtained by classifying the dry powder and the calcined powder of the hafnic acid compound described above using a sieve or the like, and the undersized particles (fine particles) may be used as the hafnic acid compound powder, regardless of whether the powder is pulverized or not. The oversized particles (coarse particles) may be pulverized again and classified. It is also possible to use a vibrating sieve into which iron balls coated with nylon or fluororesin are charged as a pulverizing medium, to perform both pulverization and classification. By performing both classification and pulverization in this way, even if there is a hafnic acid compound powder that is too large, it is possible to remove it. Specifically, when classifying using a sieve, it is preferable to use one with an opening of 150 μm to 1,000 μm. When the particle size is 150 μm to 1,000 μm, the proportion of oversized particles is not too high, so that re-pulverization is not required repeatedly, and the hafnic acid compound powder that requires re-pulverization is not classified as undersized particles.

[0072] The hafnium acid compound powder thus obtained is mixed with water or an organic solvent as a dispersion medium, and wet-pulverized using a medium such as beads to obtain a hafnium acid compound powder-containing liquid. Here, examples of the organic solvent used as the dispersion medium include alcohols, esters, ketones, aromatic hydrocarbons, aliphatic hydrocarbons, ethers, and mixed solvents thereof. Furthermore, in order to improve the film-forming properties of the hafnium acid compound film using the hafnium acid compound powder-containing liquid, a binder such as a resin component may be added. Examples of the resin component used as a binder include acrylic resin, polyurethane, epoxy resin, polystyrene, polycarbonate, glycol resin, cellulose resin, and mixed resins and copolymer resins thereof.

[0073] The hafnic acid compound film of the present invention is characterized by containing hafnic acid particles contained in the hafnic acid compound-containing material of the present invention. The hafnic acid compound film of the present invention includes a dried film obtained by applying the hafnic acid compound-containing material of the present invention to the surface of a substrate, and then drying, for example, vacuum drying, and a fired film obtained by further firing the obtained dried film.The hafnic acid compound film of the present invention also includes hafnic acid compound films having different physical properties such as crystal structure, which are generated by vacuum drying or firing the hafnic acid compound-containing material of the present invention, and may be an amorphous structure, a single crystal structure, or a polycrystalline structure.

[0074] Next, the method for producing a hafnic acid compound film of the present invention is characterized by coating, drying and / or baking the material containing a hafnic acid compound of the present invention.

[0075] Specifically, among the hafnium acid compound films of the present invention, the method for producing the dried hafnium acid compound film of the present invention includes a coating step of coating the hafnium acid compound-containing material of the present invention onto a surface of a substrate, and a film drying step of drying the hafnium acid compound-containing material coated onto the surface of the substrate to obtain a dry film.

[0076] Specifically, the hafnic acid compound-containing material obtained by the above-mentioned method for producing a hafnic acid compound-containing material of the present invention is dropped onto the surface of a substrate using a syringe while being filtered, for example, with a filter having a pore size of 2 μm, as necessary, and then applied by spin coating (1,500 rpm, 30 seconds).Then, the material is dried at 110°C or higher and lower than 300°C for 30 minutes to 12 hours to form a hafnic acid compound dry film on the surface of the substrate.

[0077] In addition, when the hafnic acid compound-containing material obtained by the above-mentioned method for producing a hafnic acid compound-containing material of the present invention is a high-viscosity liquid or gelled, it may be applied to the surface of a substrate using a brush or the like. Next, the substrate is dried at 110°C or higher and lower than 300°C for 30 minutes to 12 hours to form a hafnic acid compound dry film on the surface of the substrate. The substrate can also be dried for a long period of time, from room temperature to lower than 110°C for 1 hour to 3 days, to form the hafnic acid compound dry film of the present invention on the surface of the substrate.

[0078] Of the hafnium acid compound films of the present invention, the method for producing the calcined hafnium acid compound film of the present invention includes a coating step of coating a material containing a hafnium acid compound onto the surface of a substrate, a film drying step of drying the material containing a hafnium acid compound coated onto the surface of the substrate under atmospheric pressure or under vacuum to obtain a dried film, and a film calcination step of calcining the dried film under atmospheric pressure at a calcination temperature of 300°C or higher and 1,200°C or lower for a calcination time of 1 hour or higher and 12 hours or lower to obtain a calcined film.

[0079] Specifically, the hafnium acid compound-containing material of the present invention is applied to the surface of a substrate as described above, and the substrate having a dried hafnium acid compound film formed thereon is placed in a static furnace and fired in air at a firing temperature of 300°C or higher and 1,200°C or lower for a firing time of 1 hour or higher and 12 hours or lower, thereby forming a fired hafnium acid compound film of the present invention on the surface of the substrate.

[0080] In addition, the composite hafnium acid compound-containing material of the present invention is characterized by having the hafnium acid compound-containing material of the present invention and at least one element selected from the group consisting of Si, Al, Ti, Zn, Sn, Y, Ce, Ba, Sr, P, S, La, Gd, Nd, Eu, Dy, Yb, Nb, Li, Na, K, Mg, Ca, Zr, Mo, Ta, V, Ga, Ge, and W. It is presumed that the composite hafnic acid compound-containing material of the present invention is present in the form of ions in an ionic state in which hafnic acid and at least one element selected from the group are ionically bonded. Here, the composite hafnic acid compound-containing material of the present invention is not limited to the "containing liquid" of the present invention, but also includes a material in which a gel-like precipitate forms in the "containing liquid". The content of hafnic acid in the composite hafnic acid compound-containing material of the present invention can be determined by diluting the composition appropriately with dilute hydrochloric acid as necessary, and measuring the amount of HfO by ICP emission spectrometry (AG-5110 manufactured by Agilent Technologies) according to a method conforming to JIS K0116:2014. 2 It can be calculated by measuring the converted Hf weight fraction.

[0081] At least one element selected from the above group may be contained as a compound. Here, examples of the compound include oxides, alkali metal salts of metal acids, alkaline earth metal salts of metal acids, chlorides, metal alkoxides, polyoxometalates, etc. In addition, when the total molar content of each element in metal conversion is X, the molar ratio X / Hf of the total molar content (X) of each element in metal conversion to hafnium (Hf) may be 0.001 to 75, 0.002 to 50, 0.01 to 40, 0.2 to 30, 0.5 to 25, 0.8 to 1.5, 0.8 to 1.3, 0.9 to 1.2, or 0.9 to 1.1. In addition, when each element is P, it is converted into P, and when each element is S, it is converted into S.

[0082] In addition, the method for producing a composite hafnium acid compound-containing material of the present invention includes a step of mixing the hafnium acid compound-containing material produced by the above-mentioned method for producing a hafnium acid compound-containing material of the present invention with at least one element selected from the group consisting of Si, Al, Ti, Zn, Sn, Y, Ce, Ba, Sr, P, S, La, Gd, Nd, Eu, Dy, Yb, Nb, Li, Na, K, Mg, Ca, Zr, Ta, V, Ga, Ge, and W, to produce a composite hafnium acid compound-containing material. The composite hafnium acid compound-containing material of the present invention can be obtained by mixing the above-mentioned hafnium acid compound-containing material of the present invention with at least one element selected from the group, and keeping the liquid temperature at an appropriate temperature for a predetermined time while stirring the mixture. Here, the at least one element selected from the group, which is mixed with the hafnium acid compound-containing material produced by the above-mentioned method for producing a hafnium acid compound-containing material of the present invention, can be in various forms such as oxides, hydroxides, metal complexes, and salts made of polyoxometalates and peroxo complexes.

[0083] For example, a method for producing a liquid containing a tantalic acid compound, which is one of the elements to be mixed with the above-mentioned hafnic acid compound-containing material of the present invention, will be described below.

[0084] First, tantalum, tantalum oxide, tantalum hydroxide, or tantalum alkoxide is reacted with hydrofluoric acid (HF), such as an aqueous solution of hydrofluoric acid, to produce tantalum fluoride (H 2 TaF 7 ) and dissolving it in water to obtain an aqueous tantalum fluoride solution, which is an acidic metal solution. In the case of tantalum chloride, it is possible to omit the step of dissolving in hydrofluoric acid and to produce an acidic tantalum aqueous solution by adding water to tantalum chloride.

[0085] Here, the tantalum fluoride aqueous solution is prepared by adding water (e.g., pure water) to tantalum. 2 O 5 It is preferable to adjust the tantalum content to 1 to 100 g / L in terms of Ta 2 O 5 When the tantalum content is 1 g / L or more, it is preferable because the tantalic acid compound hydrate is easily soluble in water. When productivity is taken into consideration, the tantalum content is more preferably 10 g / L or more, and even more preferably 20 g / L or more. 2 O 5 A conversion of 100 g / L or less is preferable since it results in a tantalic acid compound hydrate that is easily soluble in water, and in order to more reliably synthesize a tantalic acid compound hydrate that is easily soluble in water, a conversion of 90 g / L or less is more preferable, a conversion of 80 g / L or less is even more preferable, and a conversion of 70 g / L or less is particularly preferable. Note that, from the viewpoint of completely dissolving tantalum or tantalum oxide, the pH of the tantalum fluoride aqueous solution is preferably 2 or less, and more preferably 1 or less.

[0086] Next, the tantalum fluoride aqueous solution is neutralized with an alkaline aqueous solution to obtain a fluorine-containing tantalum hydrate cake. Here, the alkaline aqueous solution used to neutralize the tantalum fluoride aqueous solution is preferably 10% by mass to 30% by mass of ammonia water.

[0087] The ammonia content of the ammonia water used for neutralization is preferably 10% by mass to 30% by mass. When the ammonia content is 10% by mass, tantalum is less likely to remain undissolved, and tantalum or tantalic acid can be completely dissolved in water. On the other hand, when the ammonia content is 30% by mass or less, it is preferable because it is close to a saturated aqueous solution of ammonia.

[0088] From this viewpoint, the ammonia content of the ammonia water is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, and particularly preferably 25% by mass or more, while the ammonia content is preferably 30% by mass or less, more preferably 29% by mass or less, and even more preferably 28% by mass or less.

[0089] In the above neutralization reaction, the amount of NH 3 The molar ratio of NH 2 / Ta is preferably 95 to 500, more preferably 100 to 450, and even more preferably 110 to 400. The amount of addition is determined based on the NH 2 / Ta molar ratio from the viewpoint of generating a tantalic acid compound that is soluble in amines or diluted ammonia water. 3 The molar ratio of NH / HF is preferably 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more. 3 The molar ratio of / HF is preferably 100 or less, more preferably 50 or less, and even more preferably 40 or less.

[0090] The addition time in the above-mentioned neutralization reaction is preferably within 10 minutes, more preferably within 8 minutes, and even more preferably within 5 minutes. That is, it is preferable to carry out the neutralization reaction in as short a time as possible, for example, by adding all at once, rather than gradually adding over a long period of time. The tantalum fluoride aqueous solution and ammonia water can be used at room temperature.

[0091] The fluorine-containing tantalum hydrate cake obtained by the above-mentioned neutralization reaction is decanted with dilute ammonia water using a centrifuge, and washing is repeated until the amount of liberated fluoride ions becomes 100 mg / L or less, thereby removing the fluoride ions from the fluorine-containing tantalum hydrate cake and obtaining a tantalum-containing precipitate. Since the fluorine-containing tantalum hydrate cake obtained by the above-mentioned neutralization reaction contains fluorine compounds such as ammonium fluoride as impurities, it is preferable to remove these.

[0092] The tantalum content of the obtained tantalum-containing precipitate was measured by taking a part of the tantalum-containing precipitate, drying it at 110°C for 24 hours, and then calcining it at 1000°C for 4 hours. 2 O 5 The Ta generated in this way 2 O 5 The weight of the precipitate is measured, and the tantalum content of the tantalum-containing precipitate can be calculated from the weight.

[0093] The cleaning liquid used to remove fluoride ions is preferably dilute ammonia water. Specifically, dilute ammonia water of 1 mass% or more and 35 mass% or less is preferable. In such dilute ammonia water, ammonia and ammonium ions are suitable for fluorine, and unnecessary cost increase can be avoided.

[0094] Any method can be used to remove the fluorine compounds, and examples of the method that can be used include filtration using a membrane such as reverse osmosis filtration, ultrafiltration, or microfiltration using aqueous ammonia or pure water, centrifugation, and other known methods. In addition, there is no particular need to adjust the temperature when removing fluoride ions from the fluorine-containing tantalum hydrate cake, and the removal can be carried out at room temperature.

[0095] A tertiary amine compound and pure water are added to the obtained tantalum-containing precipitate and stirred for 10 minutes to obtain a tantalum-containing mixed liquid. After that, 35% by mass of hydrogen peroxide is added to the tantalum-containing mixed liquid and stirred for 30 minutes to obtain a tantalic acid compound-containing liquid.

[0096] From the viewpoint of solubility, the tertiary amine compound is preferably mixed so that the content of the tertiary amine compound in the tantalum-containing mixed solution is 30% by mass or less, and more preferably 20% by mass or less. From the same viewpoint, the tertiary amine compound is preferably mixed so that the content of the tertiary amine compound in the tantalum-containing mixed solution is 0.1% by mass or more, and more preferably 1% by mass or more, and may be 5% by mass or more, or may be 10% by mass or more. Furthermore, the tertiary amine compound is preferably one or more selected from trimethylamine, triethylamine, and tri-n-propylamine.

[0097] The hydrogen peroxide content of the hydrogen peroxide solution is preferably 0.5% by mass to 35% by mass. The hydrogen peroxide is preferably in a molar ratio of hydrogen peroxide to tantalum of H 2 O 2 It is preferable to add hydrogen peroxide so that / Ta is 0.6 or more and 1.5 or less, and since there is a possibility that hydrogen peroxide may decompose during mixing, it is more preferable that it is 0.7 or more and 1.2 or less.

[0098] The above-mentioned method for producing a tantalic acid compound-containing liquid preferably includes a step of removing hydrogen peroxide from the obtained tantalic acid compound-containing liquid, because if hydrogen peroxide is contained in the tantalic acid compound-containing liquid, a gas generated by decomposition of hydrogen peroxide will fill the inside of a sealed container, causing the container to expand or, in the worst case, burst.

[0099] The hydrogen peroxide can be removed by any method, for example, stirring under open or reduced pressure conditions, or drying under reduced pressure.

[0100] In addition, the method for producing the liquid containing niobium acid compound, which is one of the elements mixed with the hafnium acid compound-containing material of the present invention, will be described below. Note that the description of the same part as the method for producing the liquid containing tantalic acid compound described above will be omitted.

[0101] First, niobium, niobium oxide, or niobium hydroxide is reacted with hydrofluoric acid (HF), such as an aqueous solution of hydrofluoric acid, to produce niobium fluoride (H 2 NbF 7 ) and dissolving it in water to obtain an aqueous niobium fluoride solution, which is an acidic metal solution. In the case of niobium chloride, it is possible to omit the step of dissolving in hydrofluoric acid and to produce an aqueous acidic niobium solution by adding water to niobium chloride.

[0102] Here, the niobium fluoride solution is prepared by adding water (e.g., pure water) to convert niobium to Nb 2 O 5 It is preferable to adjust the niobium content to 1 to 100 g / L in terms of Nb 2 O 5 When the niobium content is 1 g / L or more, it is preferable because the niobium compound hydrate is easily soluble in water. When productivity is taken into consideration, it is more preferable that the niobium content is 10 g / L or more, and even more preferable that the niobium content is 20 g / L or more. 2 O 5 A conversion of 100 g / L or less is preferable because it results in a niobium acid compound hydrate that is easily soluble in water, and in order to more reliably synthesize a niobium acid compound hydrate that is easily soluble in water, a conversion of 90 g / L or less is more preferable, a conversion of 80 g / L or less is even more preferable, and a conversion of 70 g / L or less is particularly preferable. Note that, from the viewpoint of completely dissolving niobium or niobium oxide, the pH of the niobium fluoride aqueous solution is preferably 2 or less, and more preferably 1 or less.

[0103] Next, the niobium fluoride aqueous solution is neutralized with an alkaline aqueous solution to obtain a fluorine-containing niobium hydrate cake. Here, the alkaline aqueous solution used to neutralize the niobium fluoride aqueous solution is preferably 10% by mass to 30% by mass ammonia water.

[0104] In the above neutralization reaction, the amount of NH 3The molar ratio of NH / Nb is preferably 95 to 500, more preferably 100 to 450, and even more preferably 110 to 400. The amount of addition is determined based on the amount of NH / Nb, from the viewpoint of the formation of a niobate compound that dissolves in amines or diluted aqueous ammonia. 3 The molar ratio of NH / HF is preferably 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more. 3 The molar ratio of / HF is preferably 100 or less, more preferably 50 or less, and even more preferably 40 or less.

[0105] The addition time in the above-mentioned neutralization reaction is preferably within 10 minutes, more preferably within 8 minutes, and even more preferably within 5 minutes.

[0106] The fluorine-containing niobium hydrate cake obtained by the above-mentioned neutralization reaction is decanted with dilute ammonia water using a centrifuge, and washing is repeated until the amount of liberated fluoride ions becomes 100 mg / L or less, thereby removing the fluoride ions from the fluorine-containing niobium hydrate cake and obtaining a niobium-containing precipitate. The fluorine-containing niobium hydrate cake obtained by the above-mentioned neutralization reaction contains fluorine compounds such as ammonium fluoride as impurities, so it is preferable to remove these. The washing liquid used to remove the fluoride ions is preferably dilute ammonia water.

[0107] The niobium content of the obtained niobium-containing precipitate was measured by taking a part of the niobium-containing precipitate, drying it at 110°C for 24 hours, and then calcining it at 1000°C for 4 hours. 2 O 5 The resulting Nb 2 O 5 The weight of the precipitate is measured, and the niobium content of the niobium-containing precipitate can be calculated from the weight.

[0108] A tertiary amine compound and pure water are added to the obtained niobium-containing precipitate and stirred for 10 minutes to obtain a niobium-containing mixed liquid. After that, 35 mass% hydrogen peroxide is added to the niobium-containing mixed liquid and stirred for 30 minutes to obtain a niobic acid compound-containing liquid.

[0109] The tertiary amine compound is preferably mixed so that the content of the tertiary amine compound in the niobium-containing mixed liquid is 0.1% by mass or more and 30% by mass or less. The tertiary amine compound is preferably one or more selected from the group consisting of trimethylamine, triethylamine, and tri-n-propylamine.

[0110] The hydrogen peroxide content of the hydrogen peroxide solution is preferably 0.5% by mass to 35% by mass. The hydrogen peroxide is preferably in a molar ratio of hydrogen peroxide to niobium H 2 O 2 It is preferable to add hydrogen peroxide so that / Nb is 0.6 or more and 1.5 or less, and since there is a possibility that hydrogen peroxide may decompose during mixing, it is more preferable that it is 0.7 or more and 1.2 or less.

[0111] As in the above-mentioned method for producing a tantalic acid compound-containing liquid, it is preferable to have a step of removing hydrogen peroxide from the obtained niobic acid compound-containing liquid.

[0112] In addition, the method for producing the titanic acid compound-containing liquid, which is one of the elements mixed with the hafnic acid compound-containing material of the present invention, will be described below. Note that the description of the same part as the method for producing the tantalic acid compound-containing liquid described above will be omitted.

[0113] First, titanium, titanium oxide, or titanium hydroxide is reacted with hydrofluoric acid (HF), such as an aqueous solution of hydrofluoric acid, to produce titanium fluoride (H 2 TiF 6 ) and dissolving it in water to obtain an aqueous titanium fluoride solution, which is an acidic metal aqueous solution. In the case of titanium chloride or titanyl sulfate, it is possible to omit the step of dissolving in hydrofluoric acid and to produce an acidic titanium aqueous solution by adding water to these.

[0114] Here, the titanium fluoride aqueous solution is prepared by adding water (e.g., pure water) to convert titanium into TiO 2 It is preferable to adjust the titanium content to 1 to 100 g / L in terms of titanium content. 2 When the titanium content is 1 g / L or more in terms of the amount of the titanium oxide, the titanium oxide hydrate is easily soluble in water, and when productivity is taken into consideration, the titanium content is more preferably 10 g / L or more, and even more preferably 20 g / L or more. 2 A titanic acid compound hydrate having a water-soluble concentration of 100 g / L or less is preferable because it will be a titanic acid compound hydrate that is easily soluble in water, and in order to more reliably synthesize a titanic acid compound hydrate that is easily soluble in water, a concentration of 90 g / L or less is more preferable, a concentration of 80 g / L or less is even more preferable, and a concentration of 70 g / L or less is particularly preferable. From the viewpoint of completely dissolving titanium or titanium oxide, the pH of the titanium fluoride aqueous solution is preferably 2 or less, and more preferably 1 or less.

[0115] Next, the titanium fluoride aqueous solution is neutralized with an alkaline aqueous solution to obtain a fluorine-containing titanium hydrate cake. Here, the alkaline aqueous solution used to neutralize the titanium fluoride aqueous solution is preferably 10% by mass to 30% by mass ammonia water.

[0116] In the above neutralization reaction, the amount of NH 3 The molar ratio of NH / Ti is preferably 95 to 500, more preferably 100 to 450, and even more preferably 110 to 400. The amount of addition is determined based on the amount of NH 3 The molar ratio of NH / HF is preferably 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more. 3 The molar ratio of / HF is preferably 100 or less, more preferably 50 or less, and even more preferably 40 or less.

[0117] The addition time in the above-mentioned neutralization reaction is preferably within 10 minutes, more preferably within 8 minutes, and even more preferably within 5 minutes.

[0118] The fluorine-containing titanium hydrate cake obtained by the above-mentioned neutralization reaction is decanted with dilute ammonia water using a centrifuge, and washing is repeated until the amount of liberated fluoride ions becomes 100 mg / L or less, thereby removing the fluoride ions from the fluorine-containing titanium hydrate cake and obtaining a titanium-containing precipitate. The fluorine-containing titanium hydrate cake obtained by the above-mentioned neutralization reaction contains fluorine compounds such as ammonium fluoride as impurities, so it is preferable to remove these. The washing liquid used to remove the fluoride ions is preferably dilute ammonia water.

[0119] The niobium content of the obtained titanium-containing precipitate was measured by taking a part of the titanium-containing precipitate, drying it at 110°C for 24 hours, and then calcining it at 1000°C for 4 hours to obtain TiO 2 The TiO 2 The weight of the precipitate is measured, and the titanium content of the titanium-containing precipitate can be calculated from the weight.

[0120] A tertiary amine compound and pure water are added to the resulting titanium-containing precipitate and stirred for 10 minutes to obtain a titanium-containing mixed liquid. After that, 35% by mass of hydrogen peroxide is added to the titanium-containing mixed liquid and stirred for 30 minutes to obtain a titanic acid compound-containing liquid.

[0121] The tertiary amine compound is preferably mixed so that the content of the tertiary amine compound in the titanium-containing mixed liquid is 0.1% by mass or more and 30% by mass or less. The tertiary amine compound is preferably one or more selected from the group consisting of trimethylamine, triethylamine, and tri-n-propylamine.

[0122] The hydrogen peroxide content of the hydrogen peroxide solution is preferably 0.5% by mass to 35% by mass. The hydrogen peroxide is preferably in a molar ratio of hydrogen peroxide to titanium of H2 O 2 It is preferable to add hydrogen peroxide so that / Ti is 0.6 or more and 1.5 or less, and since there is a possibility that hydrogen peroxide may decompose during mixing, it is more preferable that it is 0.7 or more and 1.2 or less.

[0123] As in the above-mentioned method for producing a tantalic acid compound-containing liquid, it is preferable to have a step of removing hydrogen peroxide from the obtained titanic acid compound-containing liquid.

[0124] In addition, the method for producing the liquid containing zirconium oxide compound, which is one of the elements mixed with the hafnium oxide compound-containing material of the present invention, will be described below. Note that the description of the same part as the method for producing the liquid containing tantalum oxide compound will be omitted.

[0125] First, zirconium, zirconium oxide, or titanium hydroxide is reacted with hydrofluoric acid (HF), such as an aqueous solution of hydrofluoric acid, to produce zirconium fluoride (H 2 ZrF 6 ) and dissolving it in water to obtain an acidic metal aqueous solution, that is, an aqueous zirconium fluoride solution. In the case of zirconium chloride or zirconium sulfate, it is possible to omit the step of dissolving in hydrofluoric acid and to produce an acidic titanium aqueous solution by adding water to these.

[0126] Here, the zirconium fluoride aqueous solution is prepared by adding water (e.g., pure water) to convert zirconium to ZrO 2 It is preferable to adjust the zirconium content to 1 to 100 g / L in terms of zirconium content. 2 When the zirconium content is 1 g / L or more, it is preferable because the zirconate compound hydrate is easily soluble in water, and when productivity is taken into consideration, it is more preferable that the zirconium content is 10 g / L or more, and even more preferable that the zirconium content is 20 g / L or more. 2A converted concentration of 100 g / L or less is preferable because it results in a zirconium oxide hydrate that is easily soluble in water, and in order to more reliably synthesize a zirconium oxide hydrate that is easily soluble in water, a concentration of 90 g / L or less is more preferable, a concentration of 80 g / L or less is even more preferable, and a concentration of 70 g / L or less is particularly preferable. From the viewpoint of completely dissolving zirconium or zirconium oxide, the pH of the aqueous zirconium fluoride solution is preferably 2 or less, and more preferably 1 or less.

[0127] Next, the zirconium fluoride aqueous solution is neutralized with an alkaline aqueous solution to obtain a fluorine-containing zirconium hydrate cake. Here, the alkaline aqueous solution used to neutralize the zirconium fluoride aqueous solution is preferably 10% by mass to 30% by mass ammonia water.

[0128] In the above neutralization reaction, the amount of NH 3 The molar ratio of NH 3 / Zr is preferably 95 to 500, more preferably 100 to 450, and even more preferably 110 to 400. The amount of addition is adjusted to NH 3 / Zr from the viewpoint of the formation of zirconate compounds that dissolve in amines or diluted aqueous ammonia. 3 The molar ratio of NH / HF is preferably 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more. 3 The molar ratio of / HF is preferably 100 or less, more preferably 50 or less, and even more preferably 40 or less.

[0129] The addition time in the above-mentioned neutralization reaction is preferably within 10 minutes, more preferably within 8 minutes, and even more preferably within 5 minutes.

[0130] The fluorine-containing zirconium hydrate cake obtained by the above-mentioned neutralization reaction is decanted with dilute ammonia water using a centrifuge, and washing is repeated until the amount of liberated fluoride ions becomes 100 mg / L or less, thereby removing the fluoride ions from the fluorine-containing zirconium hydrate cake and obtaining a zirconium-containing precipitate. The fluorine-containing zirconium hydrate cake obtained by the above-mentioned neutralization reaction contains fluorine compounds such as ammonium fluoride as impurities, so it is preferable to remove these. The washing liquid used to remove the fluoride ions is preferably dilute ammonia water.

[0131] The zirconium content of the obtained zirconium-containing precipitate was measured by taking a part of the zirconium-containing precipitate, drying it at 110°C for 24 hours, and then calcining it at 1000°C for 4 hours to obtain ZrO 2 The resulting ZrO 2 The weight of the precipitate is measured, and the zirconium content of the zirconium-containing precipitate can be calculated from the weight.

[0132] A tertiary amine compound and pure water are added to the obtained zirconium-containing precipitate and stirred for 10 minutes to obtain a zirconium-containing mixed liquid. After that, 35% by mass of hydrogen peroxide is added to the zirconium-containing mixed liquid and stirred for 30 minutes to obtain a zirconium oxide compound-containing liquid.

[0133] The tertiary amine compound is preferably mixed so that the content of the tertiary amine compound in the zirconium-containing mixed liquid is 0.1% by mass or more and 30% by mass or less. The tertiary amine compound is preferably one or more selected from the group consisting of trimethylamine, triethylamine, and tri-n-propylamine.

[0134] The hydrogen peroxide content of the hydrogen peroxide solution is preferably 0.5% by mass to 35% by mass. The hydrogen peroxide is preferably in a molar ratio H 2 O 2It is preferable to add hydrogen peroxide so that the ratio of Zr is 0.6 or more and 1.5 or less, and since there is a possibility that hydrogen peroxide may decompose during mixing, it is more preferable that the ratio is 0.7 or more and 1.2 or less.

[0135] As in the above-mentioned method for producing a tantalic acid compound-containing liquid, it is preferable to have a step of removing hydrogen peroxide from the obtained zirconium acid compound-containing liquid.

[0136] In addition, the method for producing the liquid containing a silicon oxide compound, which is one of the elements mixed with the hafnium oxide compound-containing material of the present invention, will be described below. Note that the description of the same part as the method for producing the liquid containing a tantalic acid compound described above will be omitted.

[0137] The method for producing a silicon oxide compound-containing liquid includes a mixing step of adding an acidic aqueous solution to a raw material containing silicon and stirring at 15°C or higher and 50°C or lower to obtain a mixed liquid containing a precursor of a silicon compound, and a stirring step of adding a solution containing an organic nitrogen compound to the mixed liquid and stirring at 15°C or higher and 50°C or lower to produce a silicon compound-containing liquid.

[0138] First, in the mixing step, an acidic aqueous solution is added to a raw material containing silicon, and the mixture is stirred at 15° C. or more and 50° C. or less to obtain a mixture containing a precursor of a silicon compound.

[0139] Examples of the silicon-containing raw material include tetraethoxysilane (TEOS), tetramethoxysilane (TMOS), sodium silicate, etc. The silicon-containing raw material preferably contains at least one of tetraethoxysilane and sodium silicate.

[0140] Examples of the acidic aqueous solution include acetic acid, hydrochloric acid, sulfuric acid, phosphoric acid, etc. The acidic aqueous solution preferably contains at least one of acetic acid, hydrochloric acid, and phosphoric acid.

[0141] When the acidic aqueous solution is acetic acid, the acetic acid content is preferably 0.001% by mass to 3.0% by mass. When the silicon-containing raw material is TEOS, the acetic acid content of 0.001% by mass or more efficiently converts the silanol ester group Si-O-CH 2 -OH 3 can be hydrolyzed to form a Si-OH structure. On the other hand, if the acetic acid content is 3.0% by mass or less, the acetic acid content in the silicon oxide compound-containing liquid, which is the final product, can be reduced, which is preferable. From this viewpoint, the acetic acid content is preferably 0.001% by mass or more, more preferably 0.005% by mass or more, and even more preferably 0.01% by mass or more. On the other hand, the acetic acid content is preferably 3.0% by mass or less, more preferably 2.5% by mass or less, even more preferably 2.0% by mass or less, particularly preferably 1.5% by mass or less, more particularly preferably 1.0% by mass or less, even more particularly preferably 0.5% by mass or less, also particularly preferably 0.1% by mass or less, even more particularly preferably 0.05% by mass or less, even more particularly preferably 0.04% by mass or less, even more particularly preferably 0.03% by mass or less, and even more particularly preferably 0.02% by mass or less. The acetic acid content described in this specification is the content when added to the raw material containing silicon in the mixing step, unless otherwise specified.

[0142] The acetic acid content in the silicon oxide compound-containing liquid is preferably 0.02% by mass to 10% by mass. The acetic acid content is more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, particularly preferably 0.15% by mass or more, and even more particularly preferably 0.2% by mass or more. On the other hand, the acetic acid content is more preferably 5% by mass or less, even more preferably 3% by mass or less, particularly preferably 1% by mass or less, and particularly preferably 0.5% by mass or less.

[0143] Furthermore, the amount of acetic acid added to the silicon-containing raw material is CH 3The molar ratio of COOH / Si is preferably 0.01 to 0.3, more preferably 0.02 to 0.25, and even more preferably 0.03 to 0.2. The time for adding acetic acid to the silicon-containing raw material is preferably 5 minutes or less, more preferably 3 minutes or less, and even more preferably 1 minute or less. The acetic acid content in the silicon oxide compound-containing liquid is preferably 0.01 to 0.3, more preferably 0.02 to 0.25, and even more preferably 0.03 to 0.2. 3 The molar ratio of COOH / Si is preferably 0.01 or more and 0.3 or less, more preferably 0.02 or more and 0.25 or less, and even more preferably 0.03 or more and 0.2 or less.

[0144] When the acidic aqueous solution added to the silicon-containing raw material is hydrochloric acid, the hydrochloric acid content is preferably 0.001% by mass to 3.0% by mass. When the silicon-containing raw material is sodium silicate, if the hydrochloric acid content is 0.001% by mass or more, sodium chloride can be efficiently produced from sodium silicate. On the other hand, if the hydrochloric acid content is 3.0% by mass or less, it is preferable because chlorine is less likely to remain in the final product, the silicon oxide compound-containing liquid. From this viewpoint, the hydrochloric acid content is preferably 0.001% by mass or more, more preferably 0.005% by mass or more, and even more preferably 0.01% by mass or more. On the other hand, the hydrochloric acid content is preferably 3.0% by mass or less, more preferably 2.5% by mass or less, even more preferably 2.0% by mass or less, particularly preferably 1.5% by mass or less, more particularly preferably 1.0% by mass or less, even more particularly preferably 0.5% by mass or less, even more particularly preferably 0.1% by mass or less, even more particularly preferably 0.05% by mass or less, even more particularly preferably 0.04% by mass or less, even more particularly preferably 0.03% by mass or less, and even more particularly preferably 0.02% by mass or less. The hydrochloric acid content described in this specification is the content when added to the silicon-containing raw material in the mixing step, unless otherwise specified, and is the value converted by the weight of HCl in 0.5N hydrochloric acid aqueous solution.

[0145] The hydrochloric acid content in the silicon oxide compound-containing liquid is preferably 0.02% by mass to 10% by mass. The hydrochloric acid content is more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, particularly preferably 0.15% by mass or more, and even more particularly preferably 0.2% by mass or more. On the other hand, the hydrochloric acid content is more preferably 5% by mass or less, even more preferably 3% by mass or less, particularly preferably 1% by mass or less, and particularly preferably 0.5% by mass or less.

[0146] The amount of hydrochloric acid added to the silicon-containing raw material is preferably such that the molar ratio of HCl / Si is 0.5 or more and 1.5 or less, more preferably 0.55 or more and 1.3 or less, and even more preferably 0.6 or more and 1.1 or less. The time for adding hydrochloric acid to the silicon-containing raw material is preferably 10 minutes or less, more preferably 5 minutes or less, and even more preferably 3 minutes or less. The content of hydrochloric acid in the silicon oxide compound-containing liquid is preferably such that the molar ratio of HCl / Si is 0.5 or more and 1.5 or less, more preferably 0.55 or more and 1.3 or less, and even more preferably 0.6 or more and 1.1 or less.

[0147] In the mixing step, after the acidic aqueous solution is added to the silicon-containing raw material, the temperature of the mixture during stirring is preferably 15° C. to 50° C., more preferably 20° C. to 45° C., and even more preferably 25° C. to 40° C. If the temperature of the mixture exceeds 50° C., the water in the mixture evaporates too much, and Si-OH undergo dehydration condensation in the mixture to form SiO 2 Fine particles may be partially formed, and may not dissolve when a solution containing an organic nitrogen compound is added during the stirring step.

[0148] Furthermore, in the mixing step, the time required for stirring after the acidic aqueous solution is added to the silicon-containing raw material varies depending on the type of silicon-containing raw material, the amount of the acidic aqueous solution added, the reduced pressure conditions, and the like.

[0149] Specifically, when the silicon-containing raw material is TEOS and the acidic aqueous solution is acetic acid, the stirring time is preferably from 30 minutes to 24 hours, more preferably from 1 hour to 15 hours, and even more preferably from 2 hours to 12 hours.

[0150] Furthermore, when the silicon-containing raw material is sodium silicate and the acidic aqueous solution is hydrochloric acid, the stirring time is preferably from 10 minutes to 10 hours, more preferably from 30 minutes to 7 hours, and even more preferably from 1 hour to 5 hours.

[0151] In this manner, an acidic aqueous solution is added to a raw material containing silicon, and the mixture is stirred at 15° C. or higher and 50° C. or lower, thereby obtaining a mixed solution containing a precursor of a silicon compound.

[0152] It is speculated that the precursor of silicon compounds, when an acidic aqueous solution is added to a raw material containing silicon, results in a linear structure of the silicic acid produced. This is speculated from the fact that the absorption maximum intensity attributable to the Si-OH stretching vibration increases in the infrared spectrum measured by a Fourier transform infrared spectrophotometer (FT-IR).

[0153] Furthermore, when the silicon-containing raw material is tetraethoxysilane and the acidic aqueous solution is acetic acid, the resulting mixture containing the precursor of the silicon compound is subjected to the next stirring step.

[0154] On the other hand, when the silicon-containing raw material is sodium silicate and the acidic aqueous solution is hydrochloric acid, the obtained mixed solution containing the precursor of the silicon compound needs to be treated as follows as a pretreatment before proceeding to the next stirring step. During the above-mentioned stirring, a part of Na in the sodium silicate reacts with a part of Cl in the hydrochloric acid, and the generated NaCl is contained in the precursor of the silicon compound, so it is advisable to remove NaCl from the precursor of the silicon compound. As a method for removing the NaCl, first, the mixed solution containing the precursor of the silicon compound is placed in a centrifuge tube and centrifuged (4500 rpm, 10 minutes) to recover the precipitated transparent gel. Next, water is added to the recovered transparent gel, which is placed in a centrifuge tube and centrifuged (4500 rpm, 20 minutes) multiple times while replacing the water, thereby removing NaCl from the precursor of the silicon compound.

[0155] Next, in the stirring step, the solution containing the organic nitrogen compound is added to the mixed liquid containing the precursor of the silicon compound, and the mixture is stirred at 15° C. or higher and 50° C. or lower to produce a silicon oxide compound-containing liquid.

[0156] Examples of the organic nitrogen compound include primary amines, secondary amines, tertiary amines, and quaternary ammonium salts. The organic nitrogen compound preferably includes at least one of primary amines, secondary amines, and quaternary ammonium salts, and specific examples include methylamine, ethylamine, dimethylamine, diethylamine, and tetramethylammonium hydroxide. A solution containing an organic acid, rather than an organic nitrogen compound, may be added to the mixture containing the precursor of the silicon compound.

[0157] The amount of the organic nitrogen compound added to the mixture containing the precursor of the silicon compound is preferably such that the molar ratio of amine / Si is 0.5 or more and 15 or less, more preferably 1 or more and 10 or less, and even more preferably 1.5 or more and 5 or less. In addition, the amount of the organic nitrogen compound added to the mixture containing the precursor of the silicon compound is preferably such that the molar ratio of amine / Si is 1.7 or more, more preferably 1.3 or more, and even more preferably 1.3 or more, from the viewpoint of generating a silicon compound that dissolves in the organic nitrogen compound. On the other hand, in terms of reducing costs, the molar ratio of amine / Si is preferably 1.5 or less, more preferably 1.2 or less, and even more preferably 1 or less.

[0158] The time for adding the organic nitrogen compound to the mixed solution containing the precursor of the silicon compound is preferably within 60 minutes, more preferably within 30 minutes, and even more preferably within 10 minutes.

[0159] In the stirring step, after the solution containing the organic nitrogen compound is added to the mixed solution containing the precursor of the silicon compound, the liquid temperature during stirring is preferably 15° C. to 50° C., more preferably 20° C. to 45° C., and even more preferably 25° C. to 40° C. If the liquid temperature during stirring exceeds 50° C., the organic nitrogen compound and the like evaporate, making it difficult for the precursor of the silicon compound to dissolve, and increasing the possibility that the precursor of the silicon compound remains.

[0160] Furthermore, in the stirring step, after adding the solution containing the organic nitrogen compound to the mixed solution containing the precursor of the silicon compound, the stirring time is preferably from 10 minutes to 24 hours, more preferably from 30 minutes to 20 hours, and even more preferably from 1 hour to 15 hours.

[0161] In this way, a solution containing an organic nitrogen compound can be added to a mixed solution containing a silicon compound precursor, and the mixture is stirred at 15° C. to 50° C. to produce a silicon oxide compound-containing liquid. As described above, it is presumed that the silicon compound precursor contains many Si-OH structures, which makes it easier to dissolve the silicon oxide in water.

[0162] In addition, the method for producing the liquid containing molybdic acid compound, which is one of the elements mixed with the hafnic acid compound-containing material of the present invention, will be described below. Note that the description of the same part as the method for producing the liquid containing tantalic acid compound described above will be omitted.

[0163] First, molybdenum or molybdenum oxide is reacted with hydrofluoric acid (HF), such as an aqueous solution of hydrofluoric acid, to produce molybdenum fluoride (H 2 MoF 6 ) and dissolving it in water to obtain an aqueous solution of molybdenum fluoride, which is an acidic metal solution.

[0164] Here, the molybdenum fluoride aqueous solution is prepared by adding water (e.g., pure water) to convert molybdenum into MoO 3 It is preferable to adjust the molybdenum content to 1 to 100 g / L in terms of molybdenum content. 3 When the molybdenum content is 1 g / L or more in terms of the molybdenum content, it is preferable because the molybdic acid compound hydrate is easily soluble in water, and when productivity is taken into consideration, it is more preferable that the molybdenum content is 10 g / L or more, and even more preferable that the molybdenum content is 20 g / L or more. 3 A molybdic acid compound hydrate having a concentration of 100 g / L or less in terms of total solubility in water is preferable, and in order to more reliably synthesize a molybdic acid compound hydrate having a high water solubility, a concentration of 90 g / L or less is more preferable, a concentration of 80 g / L or less is even more preferable, and a concentration of 70 g / L or less is particularly preferable. From the viewpoint of completely dissolving molybdenum or molybdenum oxide, the pH of the aqueous molybdenum fluoride solution is preferably 2 or less, and more preferably 1 or less.

[0165] Next, the molybdenum fluoride aqueous solution is neutralized with an alkaline aqueous solution to obtain a fluorine-containing molybdenum hydrate cake. The alkaline aqueous solution used to neutralize the molybdenum fluoride aqueous solution is preferably 10% by mass to 30% by mass ammonia water.

[0166] In the above neutralization reaction, the amount of NH 3 The molar ratio of NH / Mo is preferably 95 to 500, more preferably 100 to 450, and even more preferably 110 to 400. The amount of addition is determined based on the NH 3 The molar ratio of NH / HF is preferably 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more. 3 The molar ratio of / HF is preferably 100 or less, more preferably 50 or less, and even more preferably 40 or less.

[0167] The addition time in the above-mentioned neutralization reaction is preferably within 10 minutes, more preferably within 8 minutes, and even more preferably within 5 minutes.

[0168] The fluorine-containing molybdenum hydrate cake obtained by the above-mentioned neutralization reaction is decanted with dilute ammonia water using a centrifuge, and washing is repeated until the amount of liberated fluoride ions becomes 100 mg / L or less, thereby removing the fluoride ions from the fluorine-containing molybdenum hydrate cake and obtaining a molybdenum-containing precipitate. The fluorine-containing molybdenum hydrate cake obtained by the above-mentioned neutralization reaction contains fluorine compounds such as ammonium fluoride as impurities, so it is preferable to remove these. The washing liquid used to remove the fluoride ions is preferably dilute ammonia water.

[0169] The molybdenum content of the obtained molybdenum-containing precipitate was measured by taking a portion of the molybdenum-containing precipitate, drying it at 110 °C for 24 hours, and then calcining it at 1000 °C for 4 hours to obtain MoO3 The MoO 3 The weight of the precipitate is measured, and the molybdenum content of the molybdenum-containing precipitate can be calculated from the weight.

[0170] A tertiary amine compound and pure water are added to the obtained molybdenum-containing precipitate and stirred for 10 minutes to obtain a molybdenum-containing mixed liquid. After that, 35% by mass of hydrogen peroxide is added to the molybdenum-containing mixed liquid and stirred for 30 minutes to obtain a molybdic acid compound-containing liquid.

[0171] The tertiary amine compound is preferably mixed so that the content of the tertiary amine compound in the molybdenum-containing mixed liquid is 0.1% by mass or more and 30% by mass or less, and the tertiary amine compound is preferably one or more selected from the group consisting of trimethylamine, triethylamine, and tri-n-propylamine.

[0172] The hydrogen peroxide content of the hydrogen peroxide solution is preferably 0.5% by mass to 35% by mass. The hydrogen peroxide is preferably mixed with molybdenum in a molar ratio of H 2 O 2 It is preferable to add hydrogen peroxide so that the ratio of / Mo is 0.6 or more and 1.5 or less, and since there is a possibility that hydrogen peroxide may decompose during mixing, it is more preferable that the ratio is 0.7 or more and 1.2 or less.

[0173] As in the above-mentioned method for producing a tantalic acid compound-containing liquid, it is preferable to have a step of removing hydrogen peroxide from the obtained molybdic acid compound-containing liquid.

[0174] In addition, the method for producing the tungsten oxide compound-containing liquid, which is one of the elements mixed with the hafnium oxide compound-containing material of the present invention, will be described below. Note that the description of the same part as the method for producing the tantalum oxide compound-containing liquid described above will be omitted.

[0175] First, tungsten or tungsten oxide is reacted with hydrofluoric acid (HF), such as an aqueous solution of hydrofluoric acid, to produce tungsten fluoride (H 2MoF 6 ) and dissolving it in water to obtain an acidic metal aqueous solution, that is, an aqueous tungsten fluoride solution.

[0176] Here, the tungsten fluoride aqueous solution is prepared by adding water (e.g., pure water) to convert tungsten into WO 3 It is preferable to adjust the tungsten content to 1 to 100 g / L in terms of WO 3 When the tungsten content is 1 g / L or more, it is preferable because the tungsten acid compound hydrate is easily soluble in water, and when productivity is taken into consideration, it is more preferable that the tungsten content is 10 g / L or more, and even more preferable that the tungsten content is 20 g / L or more. 3 If the converted amount is 100g / L or less, it is preferable because the tungstic acid compound hydrate is easily soluble in water, and in order to more reliably synthesize the tungstic acid compound hydrate that is easily soluble in water, it is more preferable that the converted amount is 90g / L or less, further more preferable that the converted amount is 80g / L or less, and particularly preferable that the converted amount is 70g / L or less. Note that, in terms of completely dissolving tungsten or tungsten oxide, the pH of the tungsten fluoride aqueous solution is preferably 2 or less, more preferably 1 or less.

[0177] Next, the tungsten fluoride aqueous solution is neutralized with an alkaline aqueous solution to obtain a fluorine-containing tungsten hydrate cake. Here, the alkaline aqueous solution used to neutralize the tungsten fluoride aqueous solution is preferably 10% by mass to 30% by mass ammonia water.

[0178] In the above neutralization reaction, the amount of NH 3 The molar ratio of NH 3 / W is preferably 95 to 500, more preferably 100 to 450, and even more preferably 110 to 400. The amount of addition is determined based on the amount of NH 3 / W, from the viewpoint of the formation of a tungstic acid compound that dissolves in amines or diluted ammonia water. 3 The molar ratio of NH / HF is preferably 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more. 3The molar ratio of / HF is preferably 100 or less, more preferably 50 or less, and even more preferably 40 or less.

[0179] The addition time in the above-mentioned neutralization reaction is preferably within 10 minutes, more preferably within 8 minutes, and even more preferably within 5 minutes.

[0180] The fluorine-containing tungsten hydrate cake obtained by the above-mentioned neutralization reaction is decanted with dilute ammonia water using a centrifuge, and washing is repeated until the amount of liberated fluoride ions becomes 100 mg / L or less, thereby removing the fluoride ions from the fluorine-containing tungsten hydrate cake and obtaining a tungsten-containing precipitate. The fluorine-containing tungsten hydrate cake obtained by the above-mentioned neutralization reaction contains fluorine compounds such as ammonium fluoride as impurities, so it is preferable to remove these. It is preferable that the washing liquid used to remove the fluoride ions is dilute ammonia water.

[0181] The tungsten content of the obtained tungsten-containing precipitate was measured by taking a part of the tungsten-containing precipitate, drying it at 110°C for 24 hours, and then calcining it at 1000°C for 4 hours to obtain WO 3 The WO generated in this way 3 The weight of the precipitate is measured, and the tungsten content of the tungsten-containing precipitate can be calculated from the weight.

[0182] A tertiary amine compound and pure water are added to the resulting tungsten-containing precipitate and stirred for 10 minutes to obtain a tungsten-containing mixed liquid. Then, 35% by mass of hydrogen peroxide is added to the tungsten-containing mixed liquid and stirred for 30 minutes to obtain a tungsten acid compound-containing liquid.

[0183] The tertiary amine compound is preferably mixed so that the content of the tertiary amine compound in the tungsten-containing mixed liquid is 0.1% by mass or more and 30% by mass or less. The tertiary amine compound is preferably one or more selected from the group consisting of trimethylamine, triethylamine, and tri-n-propylamine.

[0184] The hydrogen peroxide content of the hydrogen peroxide solution is preferably 0.5% by mass to 35% by mass. The hydrogen peroxide is preferably in a molar ratio of hydrogen peroxide to tungsten H 2 O 2 It is preferable to add hydrogen peroxide so that the ratio of hydrogen peroxide to water is 0.6 to 1.5, and since there is a possibility that hydrogen peroxide may decompose during mixing, it is more preferable that the ratio of hydrogen peroxide to water is 0.7 to 1.2.

[0185] As in the above-mentioned method for producing a tantalic acid compound-containing liquid, it is preferable to have a step of removing hydrogen peroxide from the obtained tungstic acid compound-containing liquid.

[0186] In addition, the method for producing the liquid containing rare earth element acid compound, which is one of the elements mixed with the hafnium acid compound-containing material of the present invention, will be described below. Note that the description of the part that overlaps with the method for producing the liquid containing tantalum acid compound described above will be omitted.

[0187] First, a rare earth element or a rare earth oxide is reacted with hydrofluoric acid (HF), such as an aqueous solution of hydrofluoric acid, to form a rare earth fluoride, which is then dissolved in water to obtain an aqueous solution of rare earth fluoride, which is an acidic metal solution.

[0188] Here, it is preferable to adjust the rare earth fluoride aqueous solution to contain 1 to 100 g / L of rare earth element in terms of rare earth oxide by adding water (e.g., pure water). In this case, it is preferable that the rare earth element content is 1 g / L or more in terms of rare earth oxide, since it becomes a rare earth element acid compound hydrate that is easily soluble in water, and in consideration of productivity, it is more preferable that it is 10 g / L or more, and even more preferable that it is 20 g / L or more. On the other hand, it is preferable that the rare earth element content is 100 g / L or less in terms of rare earth oxide, since it becomes a rare earth element acid compound hydrate that is easily soluble in water, and in order to synthesize a rare earth element acid compound hydrate that is easily soluble in water more reliably, it is more preferable that it is 90 g / L or less, even more preferable that it is 80 g / L or less, and particularly preferable that it is 70 g / L or less. In addition, the pH of the rare earth fluoride aqueous solution is preferably 2 or less, more preferably 1 or less, from the viewpoint of completely dissolving the rare earth element or rare earth element oxide.

[0189] Next, the aqueous solution of rare earth fluoride is neutralized with an aqueous alkaline solution to obtain a fluorine-containing rare earth hydrate cake. The aqueous alkaline solution used to neutralize the aqueous solution of rare earth fluoride is preferably 10% by mass to 30% by mass ammonia water.

[0190] In the above neutralization reaction, the amount of NH 3 The molar ratio of NH to rare earth element is preferably 95 to 500, more preferably 100 to 450, and even more preferably 110 to 400. The amount of addition is determined based on the NH 3 The molar ratio of NH / HF is preferably 3.0 or more, more preferably 4.0 or more, and even more preferably 5.0 or more. 3 The molar ratio of / HF is preferably 100 or less, more preferably 50 or less, and even more preferably 40 or less.

[0191] The addition time in the above-mentioned neutralization reaction is preferably within 10 minutes, more preferably within 8 minutes, and even more preferably within 5 minutes.

[0192] The fluorine-containing rare earth element hydrate cake obtained by the above-mentioned neutralization reaction is decanted with dilute ammonia water using a centrifuge, and washing is repeated until the amount of liberated fluoride ions becomes 100 mg / L or less, thereby removing the fluoride ions from the fluorine-containing rare earth element hydrate cake and obtaining a rare earth element-containing precipitate. The fluorine-containing rare earth element hydrate cake obtained by the above-mentioned neutralization reaction contains fluorine compounds such as ammonium fluoride as impurities, so it is preferable to remove these. The washing liquid used to remove the fluoride ions is preferably dilute ammonia water.

[0193] The rare earth element content of the rare earth element-containing precipitate is determined by taking a portion of the rare earth element-containing precipitate, drying it at 110° C. for 24 hours, and then calcining it at 1000° C. for 4 hours to produce a rare earth element oxide. The weight of the rare earth element oxide thus produced can be measured, and the rare earth element content of the rare earth element-containing precipitate can be calculated from the weight.

[0194] A tertiary amine compound and pure water are added to the rare earth element-containing precipitate obtained, and the mixture is stirred for 10 minutes to obtain a rare earth element-containing mixed liquid. After that, 35% by mass of hydrogen peroxide is added to the rare earth element-containing mixed liquid, and the mixture is stirred for 30 minutes to obtain a rare earth element acid compound-containing liquid.

[0195] The tertiary amine compound is preferably mixed so that the content of the tertiary amine compound in the rare earth element-containing mixed liquid is 0.1% by mass or more and 30% by mass or less, and the tertiary amine compound is preferably one or more selected from the group consisting of trimethylamine, triethylamine, and tri-n-propylamine.

[0196] The hydrogen peroxide content of the hydrogen peroxide solution is preferably 0.5% by mass to 35% by mass. The hydrogen peroxide is preferably in a molar ratio H 2 O 2 It is preferable to add hydrogen peroxide so that / Hf is 0.6 or more and 1.5 or less, and since there is a possibility that hydrogen peroxide may decompose during mixing, it is more preferable that the ratio is 0.7 or more and 1.2 or less.

[0197] As in the above-mentioned method for producing a tantalic acid compound-containing liquid, it is preferable to have a step of removing hydrogen peroxide from the obtained rare earth acid compound-containing liquid.

[0198] The composite hafnic acid film of the present invention is characterized by containing composite hafnic acid particles contained in the composite hafnic acid compound-containing material of the present invention. The composite hafnic acid film of the present invention contains the composite hafnic acid particles contained in the composite hafnic acid compound-containing material of the present invention described above.

[0199] The method for producing a composite hafnic acid film of the present invention is characterized by comprising the steps of applying, drying and / or firing a composite hafnic acid compound-containing material produced by the method for producing a composite hafnic acid compound-containing material of the present invention described above to produce a composite hafnic acid film.

[0200] Of the composite hafnic acid films of the present invention, the method for producing the composite hafnic acid dry film of the present invention, like the method for producing the hafnic acid compound dry film of the present invention, comprises a coating step of coating the composite hafnic acid compound-containing material of the present invention onto the surface of a substrate, and a film drying step of drying the composite hafnic acid compound-containing material coated on the surface of the substrate to obtain a dry film.

[0201] Of the composite hafnic acid films of the present invention, the manufacturing method for the calcined composite hafnic acid film of the present invention, like the manufacturing method for the calcined hafnic acid compound film of the present invention, includes a coating step of coating the composite hafnic acid compound-containing material of the present invention onto the surface of a substrate, a film drying step of drying the composite hafnic acid compound-containing material coated on the surface of the substrate to obtain a dried film, and a film calcination step of calcining the dried film in air at a calcination temperature of 300°C or higher and 1,200°C or lower for a calcination time of 1 hour or higher and 12 hours or lower to obtain a calcined film.

[0202] In this specification, when "X to Y" (X and Y are any numbers) is expressed, unless otherwise specified, it includes the meaning of "X or more and Y or less", as well as "preferably greater than X" or "preferably smaller than Y". In addition, when "X or more" (X is any number) or "Y or less" (Y is any number), it also includes the meaning of "preferably greater than X" or "preferably less than Y". Effect of the Invention

[0203] The hafnium acid compound-containing material of the present invention is basic and has excellent dispersibility. [Brief description of the drawings]

[0204] [Figure 1] 1 is a table listing physical property values ​​and measurement results of hafnic acid compound-containing materials according to Examples 1 to 5 of the present invention and Comparative Example 1. [Diagram 2] 1 is a graph showing the transmittance of hafnic acid compound-containing materials according to Examples 1 to 5 of the invention and Comparative Example 1. [Diagram 3] FIG. 11 is a diagram showing the measurement results of the XRD spectrum of a hafnium acid compound-containing material according to Example 4 of the present invention. BEST MODE FOR CARRYING OUT THEINVENTION

[0205] The hafnium acid compound-containing material according to the embodiment of the present invention will be further described below with reference to the following examples, although the present invention is not limited to these examples.

[0206] Example 1 To 76.0 g of hafnium oxide (98% purity, powder, manufactured by Kojundo Kagaku Kenkyusho Co., Ltd.), 105.1 g of 55% by mass hydrofluoric acid and 796.9 g of pure water were added, heated to 80°C using a water bath, and dissolved by stirring for 24 hours to obtain a hydrofluoric acid solution of a hafnium compound. A hafnium complex was obtained by adding 2.2 g of 35% by mass hydrogen peroxide water to 60 g of the hydrofluoric acid solution of the hafnium compound. body The aqueous solution (H 2 O 2 / Hf molar ratio = 1.0), and after stirring for 5 minutes, it was gradually added to 377.2 g of 25% by mass ammonia water (NH 3 / Hf molar ratio = 250). After that, the mixture was stirred for 5 minutes to obtain a neutralized reaction solution containing hafnium hydroxide as a precipitate.

[0207] Next, the neutralized reaction liquid was decanted using a centrifuge to recover a precipitate (containing hafnium hydroxide). The recovered precipitate was mixed with 200 g of 25% by mass ammonia water to form a slurry, and then decanted again to recover the precipitate. This decantation and recovery process of the precipitate (containing hafnium hydroxide) was repeated three times.

[0208] Then, 31.1 g of 25 mass% TMAH was added to the collected precipitate (containing hafnium hydroxide) to obtain a mixed solution. 2 Pure water was added until the total weight of the mixture reached 77.7 g so that the total weight of the mixture was 6 mass % in terms of the total weight of the hafnic acid compound, and the mixture was stirred for 6 hours to obtain a colorless and transparent hafnic acid compound-containing liquid according to Example 1. The pH of the hafnic acid compound-containing liquid according to Example 1 was 14.8. The hafnic acid compound-containing liquid according to Example 1 was dried, and the resulting dried powder had an XRD maximum intensity (Ia) at a diffraction angle 2θ of 31° or more and 33° or less, which was 478.333, and an XRD maximum intensity (Ib) at a diffraction angle 2θ of 5° or more and 6° or less, which was 1255.00. The ratio Ib / Ia of the XRD maximum intensity (Ib) to the XRD maximum intensity (Ia) was 2.62.

[0209] Example 2 In Example 2, the same manufacturing method as in Example 1 was carried out except that 22.2 g of 35 mass% TEAH was added to the recovered precipitate (containing hafnium hydroxide) instead of 31.1 g of 25 mass% TMAH to obtain a mixed liquid, and a colorless and transparent hafnium acid compound-containing liquid according to Example 2 was obtained. The pH of the obtained hafnium acid compound-containing liquid according to Example 2 was 14.3. In addition, the hafnium acid compound-containing liquid according to Example 2 was dried, and the XRD maximum intensity (Ia) of the dried powder obtained at a diffraction angle 2θ of 31° or more and 33° or less was 523.333, and the XRD maximum intensity (Ib) of the diffraction angle 2θ of 5° or more and 6° or less was 785.000. The ratio Ib / Ia of the XRD maximum intensity (Ib) to the XRD maximum intensity (Ia) was 1.50.

[0210] Example 3 In Example 3, a manufacturing method similar to that of Example 1 was carried out, except that 19.4 g of 40 mass% benzyltrimethylammonium hydroxide was added to the recovered precipitate (containing hafnium hydroxide) instead of 31.1 g of 25 mass% TMAH to obtain a mixed liquid, and a colorless and transparent hafnium acid compound-containing liquid according to Example 3 was obtained. The pH of the obtained hafnium acid compound-containing liquid according to Example 3 was 14.4. In addition, the hafnium acid compound-containing liquid according to Example 3 was dried, and the XRD maximum intensity (Ia) of the dried powder obtained at a diffraction angle 2θ of 31° or more and 33° or less was 440.000, and the XRD maximum intensity (Ib) of the diffraction angle 2θ of 5° or more and 6° or less was 1083.33. The ratio Ib / Ia of the XRD maximum intensity (Ib) to the XRD maximum intensity (Ia) was 2.46.

[0211] Example 4 In Example 4, the same manufacturing method as in Example 1 was carried out except that 16.2 g of 47-50 mass% choline was added to the collected precipitate (containing hafnium hydroxide) instead of 31.1 g of 25 mass% TMAH to obtain a mixed liquid, and a colorless and transparent hafnic acid compound-containing liquid according to Example 4 was obtained. The pH of the obtained hafnic acid compound-containing liquid according to Example 4 was 14.5. In addition, the hafnic acid compound-containing liquid according to Example 4 was dried, and the XRD maximum intensity (Ia) of the dried powder obtained at a diffraction angle 2θ of 31° or more and 33° or less was 600.000, and the XRD maximum intensity (Ib) of the diffraction angle 2θ of 5° or more and 6° or less was 701.667. The ratio Ib / Ia of the XRD maximum intensity (Ib) to the XRD maximum intensity (Ia) was 1.17.

[0212] Example 5 In Example 5, 11.6 g of 47-50 mass% choline was added to the recovered precipitate (containing hafnium hydroxide) instead of 31.1 g of 25 mass% TMAH to obtain a mixed solution, and the final hafnium content was HfO 2 A manufacturing method similar to that of Example 1 was carried out, except that pure water was added so that the concentration was 10 mass % in terms of the total mass, to obtain a colorless and transparent hafnic acid compound-containing liquid according to Example 5. The pH of the obtained hafnic acid compound-containing liquid according to Example 5 was 14.5. In addition, the hafnic acid compound-containing liquid according to Example 5 was dried, and the XRD maximum intensity (Ia) of the obtained dried powder at a diffraction angle 2θ of 31° or more and 33° or less was 718.333, and the XRD maximum intensity (Ib) at a diffraction angle 2θ of 5° or more and 6° or less was 521.667. The ratio Ib / Ia of the XRD maximum intensity (Ib) to the XRD maximum intensity (Ia) was 1.38.

[0213] Comparative Example 1 The hafnium oxide compound-containing material according to Comparative Example 1 was obtained through the following steps.

[0214] First, hafnium hydroxide (HfO 2634 g of ion-exchanged water was added to 333 g of hafnium hydroxide (containing 45% by weight in terms of HfO2), to obtain an aqueous hafnium hydroxide solution. 33 g of 67.5% by weight nitric acid was added to the obtained aqueous hafnium hydroxide solution while stirring the resulting aqueous hafnium hydroxide solution, to obtain a slurry. The hafnium content of the slurry was HfO2. 2 This corresponds to 15% by weight, and the content of nitric acid was 0.5 gram equivalents per mole of hafnium.

[0215] Next, the slurry was heated to 150°C, held for 24 hours, and then allowed to stand and cool naturally, thereby obtaining a crystalline hafnia sol according to Comparative Example 1. The crystalline hafnia sol according to Comparative Example 1 was dried, and the resulting dried powder had an XRD maximum intensity (Ia) at a diffraction angle 2θ of 31° to 33° and a XRD maximum intensity (Ib) at a diffraction angle 2θ of 5° to 6°, of 1050.00 and 418.333, respectively. The ratio Ib / Ia of the XRD maximum intensity (Ib) to the XRD maximum intensity (Ia) was 0.40.

[0216] The following physical properties were measured for the hafnium acid compound-containing liquids according to Examples 1 to 5 and the crystalline hafnia sol according to Comparative Example 1. The measured physical property values ​​and the measurement methods for the physical property values ​​are shown below, and the measurement results are shown in FIG.

[0217] <Elemental analysis> If necessary, the sample was appropriately diluted with dilute hydrochloric acid and analyzed by ICP emission spectrometry (Agilent Technologies: AG-5110). 2 The converted Hf weight fraction was measured.

[0218] <pH measurement> The pH of the hafnium acid compound-containing liquids according to Examples 1 to 5 and the crystalline hafnia sol according to Comparative Example 1 was measured using an electrode (HORIBA: Standard ToupH electrode 9615S-10D) of a pH meter (HORIBA: Glass electrode type hydrogen ion concentration indicator D-51) after confirming that the liquid temperature was stabilized at 25°C. The "initial pH" in FIG. 1 refers to the pH of the hafnium acid compound-containing liquid adjusted to a liquid temperature of 25°C immediately after production. The "pH over time" in FIG. 1 refers to the pH of the hafnium acid compound-containing liquid after being left to stand for one month in an incubator set at room temperature of 25°C. It should be noted that it was difficult to measure the "pH over time" of the crystalline hafnia sol according to Comparative Example 1, since crystalline hafnia particles were precipitated.

[0219] <Transmittance measurement> 4 ml of the hafnic acid compound-containing liquid according to Examples 1 to 5 was placed in a quartz cell with an optical path length of 5.0 mm, and the transmittance of the hafnic acid compound-containing liquid according to Examples 1 to 5 at wavelengths of 550 nm, 600 nm, 650 nm, and 700 nm was measured using a spectrophotometer according to the transmittance measurement conditions described above. Then, the transmittance at wavelengths of 550 nm, 600 nm, 650 nm, and 700 nm of 70%T or more was evaluated as "◯ (GOOD)", and the transmittance less than 70%T was evaluated as "× (BAD)". The "initial transmittance" in FIG. 1 refers to the transmittance of the hafnic acid compound-containing liquid adjusted to a liquid temperature of 25°C immediately after production. The "temporary transmittance" in FIG. 1 refers to the transmittance of the hafnic acid compound-containing liquid after it has been left to stand for one month in an incubator set at room temperature of 25°C. 2 is a graph showing the transmittance of the hafnium acid compound-containing liquids according to Examples 1 to 5 and the crystalline hafnia sol according to Comparative Example 1. In FIG.

[0220] <XRD maximum intensity ratio measurement> The hafnium oxide compound-containing liquids according to Examples 1 to 5 were dried under vacuum at 150°C for 15 hours to obtain dried powders, which were then measured under the above-mentioned powder X-ray diffraction measurement conditions. Specifically, the XRD maximum intensity (Ia) at a diffraction angle 2θ of 31° to 33° and the XRD maximum intensity (Ib) at a diffraction angle 2θ of 5° to 6° were measured. Then, the ratio Ib / Ia of the XRD maximum intensity (Ib) to the XRD maximum intensity (Ia) was calculated.

[0221] <Film uniformity test> The appearance of the coating film formed on the surface of the glass substrate, which is a substitute for the current collector, was evaluated by observing it with an optical microscope. The hafnium acid compound-containing liquid according to Examples 1 to 5 was dropped onto a 15 mm x 15 mm glass substrate using a syringe, and applied by spin coating (1,500 rpm, 30 seconds). The applied portion was then dried at 60°C for 30 minutes to form a coating film on the glass substrate. The formed coating film was observed with an optical microscope at 100 times magnification, and a coating film that did not have any coarse particles and was free of bubbles, coating unevenness, and cracks was evaluated as "〇〇 (VERY GOOD)", a coating film that did not have any coarse particles but had at least one bubble, coating unevenness, or crack was evaluated as "〇 (GOOD)", and a coating film that had coarse particles and at least one bubble, coating unevenness, or crack was evaluated as "× (BAD)". "Initial film uniformity" in Fig. 1 refers to the film uniformity of a coating film formed from a hafnium acid compound-containing solution immediately after it has been produced. Also, "film uniformity over time" in Fig. 1 refers to the film uniformity of a coating film formed after leaving a hafnium acid compound-containing solution immediately after it has been produced in an incubator set at room temperature of 25°C for one month.

[0222] As shown in Fig. 1, the hafnic acid compound-containing liquids according to Examples 1 to 5 have excellent solubility in a solvent when the ratio Ib / Ia of the XRD maximum intensity (Ib) at a diffraction angle 2θ=5° to 6° to the XRD maximum intensity (Ia) at a diffraction angle 2θ=31° to 33° of the dried powder obtained by drying the hafnic acid compound-containing liquids under a vacuum atmosphere for 15 hours at 150°C is 1.1 or more. Here, Fig. 3 is a diagram showing the measurement result of the XRD spectrum of the hafnic acid compound-containing liquid according to Example 4, and the pattern seen at a diffraction angle 2θ=31° to 33° is the XRD maximum intensity (Ia), and the pattern seen at a diffraction angle 2θ=5° to 6° is the XRD maximum intensity (Ib).

[0223] The hafnium oxide compound-containing liquids according to Examples 1 to 5 were excellent in dispersibility when the maximum value of the transmittance in the wavelength region of 550 nm to 700 nm was 70%T or more.

[0224] The hafnium content in the hafnium oxide compound-containing liquid according to Examples 1 to 5 is HfO 2 When the content was more than 0 to 10% by mass, the stability was good.

[0225] The organic nitrogen compounds contained in the hafnium acid compound-containing liquids according to Examples 1 to 5 are quaternary ammonium compounds, particularly tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), choline, benzyltrimethylammonium hydroxyl, and the like. D When one or more selected from the above were used, not only was the solubility high, but also the crystallization and sol formation were highly inhibited.

[0226] When the hafnium acid compound-containing liquids according to Examples 1 to 5 had a pH of more than 7, they were basic and had excellent stability over time.

[0227] The hafnic acid compound-containing liquids according to Examples 1 to 5 were found to have excellent film uniformity when the coating films formed from these hafnic acid compound-containing liquids were observed at 100x magnification using an optical microscope.

[0228] The inventions disclosed in this specification include, in addition to the configurations of each invention or embodiment, those that are specified by changing these partial configurations to other configurations disclosed in this specification, to the extent applicable, or those that are specified by adding other configurations disclosed in this specification to these configurations, or those that are specified as higher-level concepts by deleting these partial configurations to the extent that partial action and effects are obtained. [Industrial Applicability]

[0229] The hafnium acid compound-containing material according to the present invention is basic and has high dispersibility, and is suitable as a coating material or composite material with high film adhesion and film uniformity. In addition, the hafnium acid compound-containing material according to the present invention has excellent storage stability, and the occurrence rate of defective products due to the generation of precipitates due to changes over time can be suppressed, so that waste can be reduced and the energy cost for waste disposal can be reduced. Furthermore, the hafnium acid compound-containing material according to the present invention also forms a good coating film, so that the waste can be reduced in the coated coating material as well, and the occurrence rate of defective products can be suppressed. These points lead to the achievement of sustainable management and efficient benefits of natural resources, as well as decarbonization (carbon neutralization).

Claims

1. A hafnium acid compound-containing material containing hafnium, an organic nitrogen compound, and a solvent, The organic nitrogen compound is at least one selected from the group consisting of tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), choline, and benzyltrimethylammonium hydroxide; The hafnium oxide compound-containing material is dried at 150° C. for 15 hours under a vacuum atmosphere, and the dried powder is characterized in that the ratio Ib / Ia of the XRD maximum intensity (Ib) at a diffraction angle 2θ of 5° to 6° to the XRD maximum intensity (Ia) at a diffraction angle 2θ of 31° to 33° is 1.1 or more.

2. A hafnium acid compound-containing material containing hafnium, an organic nitrogen compound, and a solvent, The organic nitrogen compound is at least one selected from the group consisting of tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), choline, and benzyltrimethylammonium hydroxide; A material containing a hafnium acid compound, characterized in that the maximum transmittance in the wavelength range of 550 nm to 700 nm is 70% T or more.

3. The hafnium content in the hafnium oxide compound-containing material is HfO 2 The hafnium acid compound-containing material according to claim 1 or 2, characterized in that the hafnium acid compound-containing material has a hafnium acid compound content of more than 0 to 10 mass % in terms of hafnium oxide converted into hafnium oxide.

4. 3. The hafnium acid compound-containing material according to claim 1, further comprising hydrogen peroxide.

5. 3. The hafnium acid compound-containing material according to claim 1, further comprising water.

6. 3. The hafnium acid compound-containing material according to claim 1, characterized in that the pH of the hafnium acid compound-containing material is greater than 7.

7. The hafnium oxide compound-containing material according to claim 1 or 2, characterized in that the maximum transmittance of the hafnium oxide compound-containing material in the wavelength range of 550 nm to 700 nm is 90% T or more.

8. adding an acidic hafnium aqueous solution containing hafnium to an alkaline aqueous solution to produce a hafnium-containing precipitate; a step of adding an organic nitrogen compound to the hafnium-containing precipitate slurry obtained by forming the hafnium-containing precipitate into a slurry form, thereby producing a material containing a hafnium acid compound; having The method for producing a hafnium acid compound-containing material, wherein the organic nitrogen compound is at least one selected from the group consisting of tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), choline, and benzyltrimethylammonium hydroxide.

9. A hafnic acid compound powder comprising the hafnic acid particles contained in the hafnic acid compound-containing material according to claim 1 or 2.

10. 3. A method for producing a hafnium oxide compound powder, comprising the step of drying and / or calcining the hafnium oxide compound-containing material according to claim 1 or 2 to produce hafnium oxide powder.

11. A hafnic acid compound film comprising hafnic acid particles contained in the hafnic acid compound-containing material according to claim 1 or 2.

12. 3. A method for producing a hafnic acid compound film, comprising coating a material containing a hafnic acid compound according to claim 1 or 2, and drying and / or baking the material.

13. A composite hafnium acid compound-containing material, characterized in that it comprises the hafnium acid compound-containing material according to claim 1 or 2, and at least one element selected from the group consisting of Si, Al, Ti, Zn, Sn, Y, Ce, Ba, Sr, P, S, La, Gd, Nd, Eu, Dy, Yb, Nb, Li, Na, K, Mg, Ca, Zr, Mo, Ta, V, Ga, Ge, and W.

14. A method for producing a composite hafnium acid compound-containing material, comprising the steps of: mixing a hafnium acid compound-containing material produced by the method for producing a hafnium acid compound-containing material according to claim 8 with at least one element selected from the group consisting of Si, Al, Ti, Zn, Sn, Y, Ce, Ba, Sr, P, S, La, Gd, Nd, Eu, Dy, Yb, Nb, Li, Na, K, Mg, Ca, Zr, Mo, Ta, V, Ga, Ge, and W; and producing a composite hafnium acid compound-containing material.

15. A composite hafnic acid compound film comprising composite hafnic acid particles contained in the composite hafnic acid compound-containing material according to claim 13.

16. A method for producing a complex hafnic acid compound film, comprising coating, drying and / or firing a material containing a complex hafnic acid compound produced by the method for producing a material containing a complex hafnic acid compound according to claim 14.

Citation Information

Patent Citations

  • Coating liquid for forming colored thin film and colored thin film obtained by the same

    JP1995326308A

  • Method for producing high-purity amorphous compound powder

    JP2001089111A

  • Process for producing sol and method for water repellent treatment of base material

    JP2003301167A

  • Precursor for forming hafnium oxide film, method for forming hafnium oxide film, capacitor structure, transistor structure, and electronic element

    JP2004104111A

  • Method for producing hafnium amide complex and hafnium-containing oxidized film

    JP2010132577A